Integrated crop-livestock systems in semiarid regions improve sheep performance compared to traditional use of natural rangelands: Nutrient digestibility, biochemical parameters, microbial protein and carcass traits - Claudenilde de Jesus Pinheiro Costa; Jheiny Rafaela Carvalho Lima; Rodrigo Barbosa de Medeiros; Maria Luana Medeiros; Arthur Lucas Julio Silva; Anderson da Silva Sales Torres; Thaysa Rodrigues Torres; Francisco Fernando Ramos de Carvalho; Márcio Vieira da Cunha; Mércia Virginia Ferreira dos Santos; José Carlos Batista Dubeux; Evaristo Jorge Oliveira de Souza (Small Ruminant Research, 2026)

Climate change projections of probable maximum precipitation over large areas through depth-area-duration analysis: A case study in Brazil - João Paulo Lyra Fialho Brêda; Walter Collischonn; Pedro Torres Miranda; Rodrigo Cauduro Dias de Paiva (Journal of Hydrology, 2026)

Hybrid magnetic GO·CNT·Fe3O4 nanomaterial for escitalopram removal: Synthesis, characterization, adsorption mechanisms, and biosafety assessment - Leonardo Vidal Zancanaro; Taíse Regina Schuster Montagner; Najla AlMasoud; Taghrid S. Alomar; Franciane Batista Nunes; Theodoro da Rosa Salles; Alana Torres Viero; Claudir Gabriel Kaufmmann Junior; Arthur Harres de Oliveira; Bernhard Westermann; Alencar Kolinski Machado; Sérgio Roberto Mortari; et al. (Journal of Environmental Chemical Engineering, 2026)

Anatomopathological aspects of osteoarticular lesions associated with Rhodococcus equi infection in two foals - Felipe Martins Pastor; Suzyane Oliveira Barros; Letícia Fernandes Campos; Acácia Eduarda de Jesus Nascimento; Gabriel Henrique Guimarães; Carlos Renato de Souza Guimarães Filho; Luis Ernesto Campos Torres; Pâmela Aparecida de Lima; Andressa Batista da Silveira Xavier; Rodrigo Otávio Silveira Silva; Roberto Maurício Carvalho Guedes; Rogéria Serakides; et al. (Veterinary Research Communications, 2026)
Rhodococcus equi is an important bacterium that affects foals up to six months of age, especially those that are immunocompromised. The main manifestation is pyogranulomatous pneumonia; nevertheless, extrapulmonary lesions have not only been reported, but are not uncommon, including arthritis and osteomyelitis. Despite the widespread occurrence of rhodococcosis, the macro- and microscopic lesions in the musculoskeletal system are still poorly understood, and a detailed study is needed to better understand the pathogenic potential of the organism. The aim of this report is to present the anatomopathological aspects of bone and joint lesions associated with Rhodococcus equi in two foals. The first case was a two-month-old male Quarter Horse foal with suspected cervical trauma. This horse was admitted in lateral recumbency, semi-comatose, and with atlantoaxial region enlarged. Necropsy revealed atlantooccipital arthritis with pyogranulomatous osteomyelitis, resulting in pathologic fractures of the atlas. There was also pyogranulomatous pachymeningitis leading to compressive myelopathy. In the second case, a two-month-old Brazilian Sport Horse foal presented with lameness of the left pelvic limb and enlargement of the left femorotibial and femoropatellar and right scapulohumeral joints. Necropsy revealed femorotibial and femoropatellar arthritis and purulent osteomyelitis in the femur, as well as extensive necrosis and bone rarefaction with focal detachment of the epiphyseal plate. Both animals had pyogranulomatous pneumonia and lymphadenitis with extracellular and intracytoplasmic gram-positive coccobacilli in neutrophils and macrophages. In the first case, R. equi was isolated and confirmed by MALDI-TOF. R. equi infection should be considered in the differential diagnosis of osteoarticular lesions in foals.

Comparison between different sun drying methods for dried vine production in relation to Aspergillus section Nigri presence and ochratoxin A accumulation - Yamila G. Kuhn; Susana G. Ferreyra; Eugenia Cendoya; Carolina Torres-Palazzolo; Eimi Riveira; Maria Laura Chiotta; Rodrigo Espindola; María Laura Ramirez; Mariana Combina; María Lorena Ponsone (International Journal of Food Microbiology, 2026)

A One Health approach to investigate potential association between producing aspects and antibiotic resistance in the dairy production chain, based on Escherichia coli as sentinel - Milimani Andretta; Rafaela de Melo Tavares; Bruna Torres Furtado Martins; Rodrigo Alves Barros; Luciano dos Santos Bersot; Ricardo Seiti Yamatogi; Brooke Monroe Ramay; Luís Augusto Nero (International Dairy Journal, 2026)

Enhancing aquaculture efficiency: Development of a reliable cryopreservation protocol for Leiarius marmoratus - Eduardo Thomé Nicoleti; Rômulo Batista Rodrigues; Jhony Lisboa Benato; Nathalia Dos Santos Teixeira; Louise Nex Spica; Larise Caroline Oliveira Lima; Gregory Brayan Valdivia-Guitiérrez; Thaiza Rodrigues de Freitas; Karel Gelina Torres-Lozano; Rodrigo Yutaka Dichoff Kasai; Darci Carlos Fornari; Jayme Aparecido Povh; et al. (Cryobiology, 2026)

Climate change and conservation of threatened tree species in the Doce River Basin: an ecological niche modeling approach - Cecília Loren-Silva; Rodrigo Gomes Gorsani; Alex Josélio Pires Coelho; Carlos Mário Galván-Cisneros; Rafaela Brandão-Gomes; Renato Augusto Ferreira de Lima; Carlos Moreira Miquelino Eleto Torres; Nathália Silva; Marcelo Simonelli; Markus Gastauer; Fabiana Bonani; João Augusto Alves Meira-Neto (Biodiversity and Conservation, 2026)
Tropical forests, particularly the Atlantic Forest, are among the most biodiverse and threatened ecosystems on Earth. Intense fragmentation, historical deforestation, and climate change have compromised their integrity and endangered endemic and rare species. The situation is even more critical in the Doce River Basin (DRB), a biodiversity hotspot in southeastern Brazil, due to the expansion of pastureland and mining, as well as the 2015 Mariana disaster. Understanding how future climate may affect the persistence of threatened tree species in the region is essential. This study evaluated the effects of climate scenarios on the distribution of 26 rare and/or threatened tree species in the DRB. We used Species Distribution Models (SDMs), combining algorithms (GLM, RDF, SVM, MaxEnt) into a consensus ensemble model under SSP3-7.0 and SSP5-8.5 scenarios for 2050 and 2090. Climatic, topographic, and edaphic variables were predictors, with climate explaining most environmental variation. Among the 26 species, 19 are projected to lose over 75% of their suitable area, with local extinction likely for range-restricted and specialized species such as Handroanthus arianeae and Grazielodendron rio-docensis . Species associated with mature forests and humid microclimates were most severely affected, while some generalists showed resilience, maintaining or expanding suitable areas. Although all species retain some suitable habitats within Protected Areas (PAs), results indicate the current PA network will be insufficient for long-term conservation. Complementary strategies such as assisted translocation, habitat connectivity, and priority-area identification based on climate projections are needed. This study provides critical insights for policies and land-use planning aimed at conserving the DRB’s threatened flora.

Invasive honeybees exacerbate the low reproductive success of a bat-pollinated tree - Víctor Rosas-Guerrero; Rodrigo Lucas-García; Lorena Alemán-Figueroa; Mariana Ceballos-Torres (Journal of Plant Research, 2026)

Seismic behaviour of aggregated reinforced masonry dwellings considering the combined influence of diaphragm stiffness and height irregularity - Rodrigo Hermosilla-Osorio; Beatriz González-Rodrigo; Nicola Tarque; Sebastian Torres-Olivares; Erick I. Saavedra Flores (Bulletin of Earthquake Engineering, 2026)
Aggregate dwellings are a common construction configuration in urban environments in the Americas, where space constraints favour terraced construction. However, seismic interaction between adjacent dwellings can significantly alter their structural response, especially when there are differences in height or in the stiffness of horizontal diaphragms. Despite advances in the seismic analysis of masonry buildings, most previous studies address these factors independently, without considering their combined effect in structurally heterogeneous complexes. This paper analyses the seismic behaviour of clusters of terraced dwellings built with reinforced masonry using partially grouted concrete blocks (PG-RCM) through non-linear dynamic analysis. Twenty-six structural configurations are studied, composed of three units that vary simultaneously in height (one, two, and three levels) and in the stiffness of the roof diaphragm (rigid or flexible). The results show that height heterogeneity induces pounding effects that increase displacement demand at upper levels, while the combined interaction between height difference and diaphragm type with different stiffness amplifies lateral response and damage distribution, even when the most rigid units are located in apparently favourable positions. The findings show that the seismic response of aggregated dwellings cannot be assessed in isolation, as it depends on the dynamic interaction with adjacent dwellings. This study provides quantitative evidence on the combined effect of variability in height and stiffness, offering useful criteria for seismic design in contexts where this type of construction is common.

Glomalin-related soil proteins enhance soil health in the rhizospheres of Caatinga trees - George Rodrigues Lambais; Rodrigo Santana Macedo; Renato Pereira Lima; Aldo Torres Sales; Wanderlei Bieluczyk; Maurício Roberto Cherubin (Journal of Arid Environments, 2026)

Formulation-dependent efficacy of Bacillus velezensis BEIB-46 for the biological control of Meloidogyne incognita in cotton - Willian Bergonsi; Rodrigo Gobatto; Luiz Carlos Oliveira da Silva; Natacha Melo; Daiane Ferreira; Bruno Scentinela Jacintho Paes; Cláudio Marcelo Gonçalves de Oliveira; Mateus Torres Nazari (European Journal of Plant Pathology, 2026)
Meloidogyne incognita is one of the main phytonematodes affecting cotton productivity, requiring sustainable control alternatives to chemical nematicides. This study evaluated the efficacy of different bioinputs based on Bacillus velezensis BEIB-46 for the biological control of M. incognita and their effects on cotton development. The strain was identified through high-resolution genomic analyses, followed by production via submerged fermentation and formulation into four distinct forms: fermented broth (6 × 10⁸ CFU/mL), fermented broth supplemented with 10% composting extract (4 × 10⁸ CFU/mL), concentrated wet biomass of B. velezensis BEIB-46 (1 × 10 1 ⁰ CFU/g), and concentrated dry biomass of B. velezensis BEIB-46 (1 × 10 1 ⁰ CFU/g), applied at different doses at planting. After 98 days, the final nematode population, reproduction factor, control efficiency, and agronomic parameters were evaluated. All B. velezensis treatments significantly reduced the M. incognita population compared with the untreated control. The highest control efficiencies were observed for the concentrated formulations, particularly the dry solid form, which achieved up to 83.4% efficiency and reproduction factors of 0.4 and 0.3. In addition to nematode suppression, the treatments significantly increased fresh root mass and shoot dry mass, indicating a biostimulant effect. The concentrated dry formulations (2 and 5 g/ha) demonstrated superior performance by combining high nematicidal efficiency with root or shoot growth promotion, as well as improved commercial attributes and operational feasibility, highlighting the potential of B. velezensis BEIB-46 as a sustainable alternative for the management of M. incognita in cotton cultivation.

Sperm Morphometric Subpopulations as the Seasonal Biomarkers of Sperm Quality in Squirrel Monkeys (Saimiri collinsi) - Wlaisa Vasconcelos Sampaio; Danuza Leite Leão; Patricia da Cunha Sousa; Elaine Cristina Batista Torres; Airton Renan Bastos Soares; Rodrigo Yudi Palhaci Marubayashi; Helder Lima de Queiroz; Sheyla Farhayldes Souza Domingues (International Journal of Primatology, 2026)
Sperm subpopulations are distinct cell clusters that define sperm function and serve as biomarkers for optimizing donor selection and reproductive success in seasonally breeding species. Male squirrel monkeys ( Saimiri collinsi , an Amazonian primate), exhibit marked seasonal reproduction linked to the fattening phenomenon, an androgen-dependent weight gain coinciding with the mating season. We investigated sperm subpopulations and semen quality in this primate across fattening and non-fattening periods. We collected semen samples monthly via electroejaculation from eight males over 14 months and assessed the samples for sperm motility, vigor, membrane functionality and integrity, morphology, and morphometry. Statistical analyses, including principal component and generalized linear mixed models, revealed three subpopulations. Subpopulation 1 (39% of the variation) was stable across periods and featured sperm with rounded heads adapted for motility in viscoelastic media, such as seminal coagulum. Subpopulation 2 (27%) predominated during the non-fattening period, showing smaller heads and an increased in major defects, likely due to epididymal stasis. Conversely, subpopulation 3 (33%) significantly increased during the fattening period, exhibiting large, elongated heads. The maintenance of high proportions of normal morphology across periods, despite seasonal shifts in subpopulation frequencies, suggests that postcopulatory sexual selection maintains high-quality standards, with the fattening period representing the physiological peak for adapted phenotypes. Our findings show that ejaculate composition is seasonally modulated, with different subpopulations predominating in each period. Subpopulation analysis is a useful predictive tool for evaluating seasonal semen quality in S. collinsi , with implications for sample selection and the advancement of assisted reproductive biotechnologies for primate conservation.

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Proteomic investigation of skeletal muscle helps explain changes in intramuscular fat content of crossbred young bulls finished in feedlot - Rodrigo de Nazaré Santos Torres; Helena Graciani Arantes; Luis Artur Loyola Chardulo; Welder Angelo Baldassini; Cassio Cantador Spadoto; Leonardo Raitz Petri; Otávio Rodrigues Machado Neto (Livestock Science, 2026)

Modeling extreme precipitation in South America using climate indices: an interpretable linear framework - Rodrigo Hierro; Pablo Llamedo; Peter Alexander; Alejandro de la Torre (Theoretical and Applied Climatology, 2026)

Zinc deficiency and sarcopenia define a metabolic frailty phenotype predicting hepatic encephalopathy and early mortality in cirrhosis - Osvely Méndez-Guerrero; Anaisa Carranza-Carrasco; Rodrigo Guerrero-Guerrero; Lilia Castillo-Martínez; Fabiola M. Del Razo-Olvera; Liliana Juárez-Martínez; Rodrigo Otero-Otero; Alma Estanes-Hernández; Patricia Clark; Carlos A. Aguilar-Salinas; Aldo Torre; Graciela E. Castro-Narro; et al. (Metabolic Brain Disease, 2026)

Biogeography of living coccolithophores in the Southeast Pacific: patterns and drivers of Gephyrocapsa spp. diversity - Francisco Díaz-Rosas; Sebastián Cornejo-Guzmán; Rodrigo Torres; Eduardo Menschel; Samuel Hormazabal; Catharina Alves-de-Souza; Peter von Dassow (Progress in Oceanography, 2026)

Rats’ preferences in the suboptimal-choice procedure are affected by the perceptual salience of the stimuli - Rodrigo González-Torres; J. Alfredo Zarco-Morales; Montserrat García-Lugo; Vladimir Orduña (Behavioural Processes, 2026)

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Chilean Blue Whales: Fidelity to Feeding Areas and Migratory Connectivity With the Eastern Tropical Pacific 1 - Barbara Galletti Vernazzani; Elsa Cabrera; Paula A. Olson; Diego Cortés‐Peña; Isabella L. K. Clegg; Sonia Español‐Jimenez; Verena Häussermann; Rodrigo Hucke‐Gaete; Rodrigo Moraga; Daniel M. Palacios; Guido Pavez; María José Perez‐Alvarez; et al. (Marine Mammal Science, 2026)
In the Eastern South Pacific (ESP), blue whale ( Balaenoptera musculus subsp.) aggregations have been described for two feeding areas (in northern and southern Chile) and in the Eastern Tropical Pacific (ETP). However, despite the knowledge of these areas, little is known about the seasonal movements of blue whales between them. Comparisons of 1074 individual blue whales, photographed across these regions from 1992 to 2019, resulted in re‐sightings of 107 individuals. Photo‐identification comparisons were conducted using the Southern Hemisphere Blue Whale Catalog, a collaborative platform for sharing photo‐identification data among 21 research groups from 7 nations. A total of 92 matches were found within the southern Chile feeding area and 13 matches within the northern Chile feeding area. High site fidelity was found for the southern Chile feeding area (return rates ≥ 43%). The longest interval between the first and last sighting was 17 years. There was no exchange between northern and southern Chile feeding areas. Two matches revealed long‐distance connectivity and migration of blue whales from southern Chile to the Galápagos Islands in the southern ETP. There were no matches between Chile and the Costa Rica Dome, farther north in the ETP, a location known for the year‐round presence of blue whales. The results highlight the importance of collaboration to understand blue whale movements and migration patterns. Our results provide valuable ESP and ETP region‐wide data toward understanding population structure and informing conservation and management strategies, population assessments, and/or delineating biologically important areas.

Age and growth of the endemic g roovebelly stingray ( Dasyatis hypostigma ), a heavily exploited batoid in the B razilian Meridional Margin (21–34° S ) - Giovanni Arlan Torres; Rodrigo Silvestre Martins; Luciano Gomes Fischer; Luís Gustavo Cardoso; Rodrigo Sant'Ana; Bruno Mourato (Journal of Fish Biology, 2026)
Life‐history data are often lacking for exploited elasmobranchs, jeopardizing proper management and conservation measures for this vulnerable group. Herein, we provided age and growth estimates for the groovebelly stingray ( Dasyatis hypostigma ), a medium‐sized, heavily exploited batoid endemic to the southwestern Atlantic Ocean. Ages were estimated from vertebral centra, including 201 males and 71 females, with sizes varying between 150 and 580 mm in disc width (DW). Observed ages ranged from 0 to 10 years in males and from 0 to 11 years in females. Edge type analysis indicates that band‐pairs are seasonally formed once a year. Among multiple growth models fitted with a Bayesian framework, the logistic model best describes the growth in terms of biological realism and statistical robustness. Females attained larger asymptotic sizes and had lower growth coefficients than males. Growth parameters were comparable to that of D. hypostigma from Uruguayan and Argentinian waters, although males seem to grow faster in Brazilian waters.

Therapeutic Window of Morphine on Cardiac and Respiratory Parameters of Juvenile Tambaqui, Colossoma macropomum - Brenda Maria Pereira Alho da Costa; Joelson da Silva Farias; Rodrigo Gonçalves dos Santos; Clarissa Araújo da Paz; Luana Vasconcelos de Souza; Luciana Eiró Quirino; Murilo Farias dos Santos; Marcelo Victor dos Santos Brito; Marcelo Ferreira Torres; Moisés Hamoy; Luis André Luz Barbas (Fishes, 2026)
Morphine is widely used as an analgesic in vertebrates, yet its cardiorespiratory safety and effective therapeutic range remain poorly explored in fish. This study investigated the dose-dependent effects of morphine on cardiac and respiratory parameters of juvenile tambaqui (Colossoma macropomum). Juveniles (25.95 ± 4.08 g) were randomly assigned to control, sham (0.9% saline) or morphine groups (24, 28, 32, 36 and 40 mg kg−1, i.p.). Electrocardiogram (ECG) recordings were used to assess heart rate (HR), PQ, RR and QT intervals, and QRS amplitude, while opercular beat rate (OBR) and opercular beat intensity (OBI) were measured to evaluate respiratory responses. Morphine induced a significant dose-dependent bradycardia and QT prolongation, without affecting QRS amplitude or conduction integrity. Respiratory frequency and intensity also decreased with increasing doses, with responses plateauing above 32 mg kg−1. The EC50 for HR reduction was 27.18 mg kg−1, aligning with a safe therapeutic range of 24–32 mg kg−1. By establishing this dose–response dynamic, the study provides the first characterization of a physiologically safe therapeutic window of morphine in tambaqui and highlights its safety profile for cardiorespiratory parameters. Moreover, the present results demonstrate that the opioid system of juvenile tambaqui is functionally developed, providing a physiological basis for future studies on nociception and analgesic efficacy, with relevance to welfare-oriented practices in aquaculture.

Shaping soil fungal communities: How swine waste treatment systems and geography drive fungal community shifts - Camila Diehl; Gabriela Merker Breyer; Mariana Costa Torres; Camila Rosana Wuaden; Raquel Rebelatto; Janaina Pastore; Rodrigo da Silveira Nicoloso; Marcio Dorn; Jalusa Deon Kich; Franciele Maboni Siqueira (Science of The Total Environment, 2026)

From farm to environment: the microbiome and the silent spread of antimicrobial resistance genes in soil despite manure management in swine farms - Gabriela Merker Breyer; Mariana Costa Torres; Raquel Rebelatto; Camila Rosana Wuaden; Janaina Pastore; Mateus Lazzarotti; Rodrigo da Silveira Nicoloso; Márcio Dorn; Jalusa Deon Kich; Franciele Maboni Siqueira (Journal of Environmental Management, 2026)

Comprehensive thermochemical assessment of pear waste pyrolysis for energy recovery: Insights into decomposition kinetics, gas evolution, and product characterization - Rodrigo Torres-Sciancalepore; Andrés Reyes-Urrutia; Rosa Rodriguez; Gastón Fouga; Germán Mazza (Journal of Environmental Chemical Engineering, 2026)

Longitudinal study of frequency of diarrhea and rotavirus species A in suckling calves from a small-scale family dairy farm in Brazil - Geovana Depieri Yoshitani; André de Sá Ribeiro; Elisabete Takiuchi; Rodrigo Alejandro Arellano Otonel; Juliana Torres Tomazi Fritzen; Alice Fernandes Alfieri; Amauri Alcindo Alfieri (Veterinary Research Communications, 2026)

Chemical investigation and evaluation of the antibacterial and antioxidant activities of ethanolic extracts from ten specimens of Cereus jamacaru DC. (Cactaceae) - Maria José Rejane Oliveira Almeida; José Jailson Lima Bezerra; Daniel Rodrigo Cavalcante de Araújo; Juliana Gomes Freitas; Fabiane Rabelo da Costa Batista; Bruno Oliveira de Veras; Márcia Vanusa da Silva; Francisco das Chagas Lima Pinto; Maria da Conceição de Menezes Torres (South African Journal of Botany, 2026)

Short- and long-term effects of social hierarchy level on seminal quality and behavior traits in goat bucks - José R. Haro-Torres; Gustavo Ramírez-Valverde; Saúl Hernández-Aquino; Rodrigo Flores-Garivay; Lorenzo Buenabad-Carrasco; Juan González-Maldonado (Tropical Animal Health and Production, 2026)
Social hierarchy affects semen quality and social interactions in males. However, the long-term effects of social hierarchy on semen quality, sexual, and social traits in goat bucks are unknown. Goat bucks were assigned to the dominant and subordinate groups. Semen quality, sexual, and social behavior traits were evaluated every other day for six days to establish a short-term effect, and every week for 25 weeks to establish a long-term effect of social hierarchy. There was not a short-term effect ( P > 0.05) of social hierarchy in social and sexual behavior traits, but dominant males produced seminal samples with higher ( P < 0.05) progressive motility than subordinate males. There was a long-term effect on social and sexual behavior, but no changes were related to semen quality traits. The subordinate males received more hits during feeding time ( P < 0.05), and they performed a lower number of vocalizations than dominant males ( P < 0.05). In conclusion, social hierarchy affects the semen quality in the short-term, and social and sexual behavior traits in the long-term.

Design and performance of the Low-Energy Module for the Ziré instrument on the NUSES mission: A compact spectrometer for low-energy particles in space high-radiation environments - Muhammd Abdullahi; Roberto Aloisio; Francesco Arneodo; Sindorjon Ashurov; Uygar Atalay; Felicia C.T. Barbato; Roberto Battiston; Mario Bertaina; Elisabetta Bissaldi; Denise Boncioli; Leonid Burmistrov; Franck Cadoux; et al. (Advances in Space Research, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Comparative genotoxicity as a baseline protocol for assessing environmental quality in Brazilian Marine Protected Areas: A case study of Grapsus grapsus (Brachyura: Grapsidae) from Trindade and Fernando de Noronha islands - Mônica L. Adam; Rodrigo A. Torres; Harry Boos; Anderson R.B. Lima; Marcelo A.A. Pinheiro (Regional Studies in Marine Science, 2025)

Enhancing aquaculture efficiency: Development of a reliable cryopreservation protocol for leiarius marmoratus - Eduardo Thomé Nicoleti; Rômulo Batista Rodrigues; Jhony Lisboa Benato; Nathalia Dos Santos Teixeira; Louise Nex Spica; Larise Caroline Oliveira Lima; Thaiza Rodrigues de Freitas; Karel Gelina Torres Lozano; Rodrigo Yutaka Dichoff Kasai; Jayme Aparecido Povh; Danilo Pedro Streit (Cryobiology, 2025)

Regression model for predicting beef carcass cutability in crossbred beef cattle - Welder A. Baldassini; Victor G. L. da Fonseca; Marcelo A. S. Coutinho; Gregori Rovadoscki; Rick A. F. Mangueira; Rodrigo N. S. Torres; Otávio R. Machado Neto; Guilherme L. Pereira; Rogério A. Curi; Luis Artur L. Chardulo (Tropical Animal Health and Production, 2025)

Probabilistic characterization of inherent and epistemic geotechnical uncertainty in soil constitutive models using polynomial chaos expansion and monotonic drained triaxial tests - Francisco Pinto; César Torres; Matias Birrell; Yong Li; Jawad Fayaz; Rodrigo Astroza (Computers and Geotechnics, 2025)

Numerical study on the seismic behaviour of aggregate reinforced concrete block masonry buildings - Sebastian Torres-Olivares; Beatriz González-Rodrigo; Diego A. Hidalgo-Leiva; Nicola Tarque; Erick I. Saavedra Flores (Bulletin of Earthquake Engineering, 2025)
Current seismic codes predominantly focus on isolated structures, despite the widespread presence of building aggregates in urban environments. This issue is particularly relevant in Costa Rica, where partially grouted reinforced concrete block masonry (PG-RCM) buildings are routinely constructed directly adjacent to each other with no separation, forming aggregates through contact between independent walls rather than shared structural elements. These modern aggregate configurations, frequently built on varying ground elevations, represent a common construction practice whose complex seismic interactions are not explicitly addressed in typical design provisions. This study investigates the seismic behaviour of contemporary PG-RCM aggregates through advanced numerical modelling. The research employs non-linear dynamic analysis with bidirectional seismic excitation, using multilayered shell elements with integrated reinforcement and a damage-based material model for masonry components. The numerical model was validated against experimental data from cyclic pseudostatic loading test on individual PG-RCM wall panel. Subsequent analyses examined both isolated and aggregate configurations, with compression-only contact interactions between adjacent units modelled through zero-length elements. A five-unit aggregate model proved sufficient to capture the effects of structural interactions. The results reveal that in level-ground arrangements, damage concentrates in one end unit of the aggregate, which acts as an energy dissipator through contact-based load transfer, thereby reducing damage in adjacent units. When units are built at different elevations, a critical height difference threshold was identified, above which the highest unit consistently experiences the most severe damage, regardless of its position in the aggregate. These findings demonstrate how contact interaction between adjacent structures significantly alters their seismic response, particularly when combined with elevation differences, emphasising that these complex interactions warrant further investigation to inform the potential future development of targeted seismic design guidance.

Effects of the inclusion of a rumen-protected B-vitamin blend and hydroxy trace minerals in the diets of confined Nellore cattle on performance and cecal and ruminal histology - Maria Carolina Gonçalves de Arruda; Rodrigo de Nazaré Santos Torres; Daniela Bernadete Rozza; Luis Arthur Loyola Chardulo; Welder Angelo Baldassini; Rogério Abdallah Curi; Guilherme Luis Pereira; Iasmin Myrele Santos Calaça de Farias; Marco Aurélio Porcionato; Otávio Rodrigues Machado Neto (Animal Feed Science and Technology, 2025)

Assessing DNA damage in sentinel crabs as indicators of tourist impact in the Fernando de Noronha Archipelago, a Marine Protected Area and World Natural Heritage Site in Brazil - Mônica Lúcia Adam; Anderson Rodrigues Balbino de Lima; Marcelo Antônio Amaro Pinheiro; Harry Boos; Rodrigo Augusto Torres (Environmental Monitoring and Assessment, 2025)

Cannabidiol potentiates phenobarbital-induced cell death in the developing brain - Rubia Aparecida Fernandes; João Vitor Melo Ribeiro; Rodrigo Espindula Torres; Giovanna Bruno Borges; Larissa Gabrielly Ribeiro de Freitas; Olagide Wagner de Castro; Marcio Flávio Dutra Moraes; Norberto Garcia-Cairasco; Fabrício A. Moreira; Victor Rodrigues Santos (NeuroToxicology, 2025)

Forecasting Intense Radar Reflectivity Using Machine Learning and Deep Learning Algorithms - Ximena Orsi; Rodrigo Hierro; Pablo Llamedo; Pedro Alexander; Alejandro de la Torre (International Journal of Climatology, 2025)
Over the past 50 years, numerous studies have been conducted in the Cuyo region of Argentina, South America, investigating the relationship between meteorological variables and hail precipitation. These studies have led to the development of various models aimed at classifying hydrometeors, determining their precipitation, size, and the resulting surface damage. Based on 16 years of observations using a three‐radar network in the Cuyo region, this paper presents preliminary results from a hail prediction study employing machine learning and deep learning techniques applied to radar data. Algorithms random forest (RF), gradient boosting (GB) and logistic regression (LR) in addition to a recurrent neural network, were used to predict hail occurrence based on radar data. Storm cells were classified as hail or no‐hail when their reflectivity reached or exceeded 55 dBZ during their evolution. Reflectivity was found to be the most suitable variable among over 50 radar variables for studying hail occurrence. Results showed that considering the temporal evolution of radar observations, by including data at different time steps (from Results showed that considering the temporal evolution of radar observations, by including data at different time steps (from t = 1 to t = 5), significantly improved the algorithms ability to predict hail occurrence). This can be attributed to both a reduction in forecast lead time and the relevance of the temporal evolution of the variables. The inclusion of global model data, such as reanalysis from ECMWF (ERA5) did not demonstrate any significant improvement in our predictions. Models such as recurrent neural networks (RNN) have the potential to deliver enhanced performance since they explicitly account for temporal dynamics.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Ocean acidification and elevated temperatures alter the behavior of a sub-Antarctic fish - María E. Lattuca; María E. Barrantes; Eloísa M. Giménez; Patricio H. Manríquez; Rodrigo Torres; Paolo Domenici; Myron A. Peck; Daniel A. Fernández (Marine Pollution Bulletin, 2025)

Abundance, provenance, and characteristics of plastic beverage bottles in human settlements and on beaches of the Latin American Pacific region: a citizen science study - Ostin Garcés-Ordóñez; Mauricio Ergas; Jostein Baeza-Álvarez; Daniela Honorato-Zimmer; Ninoshka López-Xalín; Nelson Vásquez; Miquel Canals; Diamela De Veer; María Elisa Aguilera; Illiana Arias; Solange Bolaños; Daphne Aguilar Fallas; et al. (Journal of Cleaner Production, 2025)

Root-Stem Transition Zone Anatomy Assessment in Hormonal Variants of Tomato, After Growing Under Contrasting Water Saturation - Rodrigo Barbosa Kloss; Felipe Della Torre; Vinícius Politi Duarte; Fabricio José Pereira; Joni Esrom Lima; Marcel Giovanni Costa França (Journal of Plant Growth Regulation, 2025)

Harpagifer bispinis, but not Patagonotothen tessellata, appears robust to interactive effects of ocean warming and acidification in southern Patagonia - Eloísa M. Giménez; Fabián A. Vanella; Laura I. Wolinski; Rodrigo Torres; María E. Lattuca (Marine Environmental Research, 2025)

Enrichment of electrochemically active microorganisms in a chlorate-pressured environment - Angela Cantillo-González; Felipe Torres-Rojas; Rodrigo De la Iglesia; Ignacio T. Vargas (Journal of Environmental Chemical Engineering, 2025)

Mitonuclear genetics reveals a novel perspective on the stock structure and fishery management of skipjack tuna (Katsuwonus pelamis) in the Atlantic Ocean - Maria Clara G. Queiroz-Brito; Fernando F. Mendonça; Joana I. Robalo; Freddy Arocha; N’Guessan Constance Diaha; Monin Justin Amandé; Fambaye Ngom Sow; Davy Angueko; Paulo Travassos; Rodrigo A. Torres (Reviews in Fish Biology and Fisheries, 2025)

Ketamine-Ethanol Combination Decreases Reduced Glutathione Levels and Activates both Intrinsic and Extrinsic Apoptotic Pathways Prior to Neuronal Death in SH-SY5Y Cells - Felype Valentim Duarte Castelhano; Carolina Aparecida de Faria Almeida; Giulia de Assis Braz; Gabriela Otofuji Pereira; Rafaela Yolanda Silvino de Almeida; Matheus Lujan Pereira; Juliana Ligia Freires Ribeiro; Karin Argenti Simon; Rodrigo Portes Ureshino; Tania Marcourakis; Larissa Helena Torres; Raphael Caio Tamborelli Garcia (Neurotoxicity Research, 2025)

A meta-analysis of the effects of monensin supplementation on beef cattle performance, digestion and ruminal parameters in three feeding systems - Richard Vaquero Ribeiro; Rodrigo de Nazaré Santos Torres; Welder Angelo Baldassini; Luis Artur Loyola Chardulo; Luis Orlindo Tedeschi; Otávio Rodrigues Machado Neto (Animal Feed Science and Technology, 2025)

Forest citizens and people‐centered conservation in the Brazilian Amazon - Luke Parry; Thiago F. Morello; James A. Fraser; Natalia Guerrero; Gabriela S. Lotta; Rodrigo C. Martins; Peter Newton; Jessica C. Pires Cardoso; Andreza A. Souza Santos; Mauricio Torres (Conservation Biology, 2025)
Demands for territorial recognition are foundational to the claiming of rights by forest‐proximate people who attempt to conserve their forests. The rights of these often‐marginalized populations have been largely overlooked by conservationists, yet they are central to achieving people‐centered conservation. We further developed the concept of forest citizenship as a normative framework and analytical tool based on Brazilian social environmentalism ( socioambientalismo ), florestania (a former political project in Acre state), Latin American scholarship on ecological citizenship, and Eurocentric political philosophy. Decades of struggle for territorial recognition and social inclusion have solidified the right to have rights for Amazonia's forest citizens. Hence, forest citizens are people who have become so through the sociopolitical dynamics of their rights claims. Forest citizenship is built on community mobilization to create legally recognized territories with participatory governance but becomes tangible only if individuals and communities can successfully claim other rights from institutions through everyday practices of citizenship. We also assessed the current number and distribution of forest citizens across Brazilian Amazonia based on gridded population data and spatial analyses to calculate the resident population in four territorial categories that meet these democratic preconditions: Indigenous lands, extractive reserves, sustainable development reserves, ecological settlement projects, and Afro‐descendent Quilombola territories. The territories covered 31% of the Legal Amazon, were home to 1.05 million forest citizens, and had diverse primary policy objectives but shared goals of empowering communities and conserving forests. To be emancipatory, forest citizenship must be bottom‐up, socially inclusive, and improve people's lives. We suggest that conservationists pay greater attention to power relations and decision‐making structures related to forest territories. Territory‐based forest citizenship may be relevant for other countries where environmentalism has intersected with struggles for land rights and democracy.

Occurrence of current-use pesticides in sediment cores from lakes and peatlands in pristine mountain areas of Brazilian national parks - Patrícia C.G. Pereira; Cláudio E.T. Parente; Yago Guida; Raquel Capella; Gabriel O. Carvalho; Pavlína Karásková; Jiří Kohoutek; Karla Pozo; Petra Přibylová; Jana Klánová; João P.M. Torres; Paulo R. Dorneles; et al. (Environmental Pollution, 2025)

Bats over rice: Assessing the contribution of insectivorous bats to pest suppression in Mexican rice fields - Cárol Sierra-Durán; Ángel Torres-Alcántara; Adrià López-Baucells; Rodrigo A. Medellín (Agriculture, Ecosystems & Environment, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Sub-Lethal Effects of Predators in Aquaculture: Assessment of Chronic Exposure to Conspecific Alarm Substance on Feeding and Growth Performances of Nile Tilapia - Rafaela Torres Pereira; Alexandre Luiz Arvigo; Caio Akira Miyai; Augusto Rysevas Silveira; Percília Cardoso Giaquinto; Helton Carlos Delicio; Leonardo José Gil Barcellos; Rodrigo Egydio Barreto (Fishes, 2025)
In aquaculture practices, fish are mostly protected from lethal actions of predators. However, sub-lethal effects can be challenging to prevent, as they may be associated with chemical cues signaling predation risk that easily dissolve and spread in water, serving as potential stressors. These cues originate from predators, stressed or injured prey releasing blood, a conspecific alarm substance (CAS), and/or other bodily fluids. In this study, we simulated a small-scale net cage system and assessed the feeding and growth of Nile tilapia exposed chronically to a CAS. Nile tilapia, an invasive species in many aquatic systems, frequently coexist freely alongside those cultivated in cages. Consequently, caged tilapia may regularly be exposed to a CAS, potentially leading to chronic stress and impacting growth and development. Fish were exposed daily to either a CAS or a control vehicle (distilled water) for 45 days (one fish per cage). Fish in both conditions exhibited similar increases in body mass, weight gain, and length over time and displayed an allometric negative growth profile, indicating that the CAS did not affect the length–weight relationship as well. Specific and relative growth rates, condition factor, body axes, food intake, and feeding conversion efficiency were also unaffected by the CAS over time. This body of evidence suggests that the CAS did not act as a chronic stressor for caged Nile tilapia and a possible explanation is habituation.

Parameterization of waves interacting with homogenous permeable breakwaters: Integrating physical and numerical models with machine learning - B. Rodrigo Covarrubias-Contreras; Alec Torres-Freyermuth; Camilo Rendón-Valdez; Christian M. Appendini; Ernesto Gray (Ocean Engineering, 2025)

Interaction between a bubble curtain with waves and currents: implications on sediment dispersal - B. Rodrigo Covarrubias-Contreras; Alec Torres-Freyermuth; Rafael O. Tinoco; Bernardo Figueroa-Espinoza (Environmental Fluid Mechanics, 2025)
Bubble curtains are widely used for different environmental applications relying on the generation of recirculation cells. Prior studies suggest that bubble curtains can modify the morphology of rivers and channels by keeping sediment in suspension, and as an alternative for sediment transport control. However, their use in coastal environments is still relatively unexplored. We investigate the interaction between the recirculation cell induced by a bubble curtain with incoming currents and waves. Laboratory experiments were carried out on a wave-current flume facility equipped with a bubble diffuser. Simulated cases considered different characteristics of the bubble curtain, water level, currents, and waves. Free-surface elevation and velocity were measured concurrently with high spatial resolution. Experimental observations show that the bubble curtain modifies wave- and current-induced velocity profiles. For unidirectional currents, as the flow approaches the curtain, the velocity magnitude decreases near the surface and increases near the bed due to the recirculation cell. In the presence of waves, the recirculation flow affects both the wave-induced velocity and asymmetry, both important parameters for sediment transport. Thus, synthetic particles were used as sediment proxy to investigate the role of the recirculation cell on the wave-induced near bed transport. Experimental results highlight the effects of both the bubble curtain recirculation cells and the structure of the diffuser itself in sediment deposition. These experiments reveal the potential of bubble curtains for modifying hydrodynamics and deposition patterns in coastal zones, and provide a novel data set which can be used for the calibration and validation of numerical models.

Development and validation of a rapid method for the determination of oil and oleic acid content in peanut (Arachis hypogaea L.) using time domain nuclear magnetic resonance - Lucas J. Carvalho; Jacqueline Elis de Souza; Evelyn de F. Guimarães; Luiz Alberto Colnago; Daniel Martelozo Consalter; Silvia Paulo de Azevedo; Cristina Torres Consalter; Karla Borba; Rodrigo Garcia; Davi dos Santos Miquelin; Bruno Felipe Caravieri; Jair Heuert; et al. (Food Research International, 2025)

CO2-assisted gasification of Patagonian rosehip bio-wastes: Kinetic modeling, analysis of ash catalytic effects, and product gas speciation - Rodrigo Torres-Sciancalepore; Daniela Nassini; Daniela Asensio; José Soria; Rosa Rodriguez; Gastón Fouga; Germán Mazza (Journal of Environmental Chemical Engineering, 2024)

Meiofaunal Dynamics in Oceanic Islands: Insights From Spatial Distribution, Substrate Influence and Connectivity - Adrián Torres‐Martínez; Rodrigo Riera (Marine Ecology, 2024)
There is an apparent contradiction between the sedentary lifestyle and direct development of meiofaunal organisms and their widely observed distribution. This study is situated within the theoretical framework of ecological connectivity, metacommunities, and the impact of substrate type, particularly in the unique context of oceanic islands, offering a crucial perspective to unravel the complexities of meiofaunal dispersal and connectivity. We here studied the spatial distribution of meiofauna on natural and artificial beaches of an oceanic island, that is, Gran Canaria (Canary Is., NE Atlantic Ocean). The results revealed higher abundance and richness of meiofauna on artificial substrates compared to natural ones, with nematodes, copepods, and annelids being the dominant groups. The meiofaunal community composition differed significantly between natural and artificial beaches, suggesting colonisation of artificial beaches by natural beach communities. Notably, certain species were exclusively found on artificial beaches. The study highlighted the importance of substrate type in influencing meiofaunal composition, with artificial beaches providing new ecological niches and resources for meiofauna. The dissimilarity between beaches was attributed to morphospecies exclusive to either artificial or natural substrates, emphasising the role of dispersal mechanisms. These findings contribute to understanding the metacommunity dynamics of meiofauna in oceanic islands and call for further research on dispersal potential and biogeography.

Corrigendum to Effects of blood metal(loid) concentrations on genomic damages in sharks [Environ. Pollut. 359 (2024) 124569] - Camila Brasilino Botêlho de Araújo; Sibele Alves de Mendonça; Danielle de Lima Viana; Mariana da Fontoura Martins; Patrícia Gomes Costa; Adalto Bianchini; Paulo Guilherme Vasconcelos de Oliveira; Rodrigo Augusto Torres; Fábio Hissa Vieira Hazin; Mônica Lúcia Adam (Environmental Pollution, 2024)

Effects of blood metal(loid) concentrations on genomic damages in sharks - Camila Brasilino Botêlho de Araújo; Sibele Alves de Mendonça; Danielle de Lima Viana; Mariana da Fontoura Martins; Patrícia Gomes Costa; Adalto Bianchini; Paulo Guilherme Vasconcelos de Oliveira; Rodrigo Augusto Torres; Fábio Hissa Vieira Hazin; Mônica Lúcia Adam (Environmental Pollution, 2024)

Use of different stocking densities of Litopenaeus vannamei juveniles using "synbiotics": effects on water quality, microorganisms, bioflocs composition and zootechnical performance - Stefani M. Santos; Wilson Wasielesky; Ítalo Braga; Rodrigo Zuñiga; Victor Torres Rosas; Anelise Christ-Ribeiro; Geraldo Kipper Fóes (Aquaculture International, 2024)

Flow-weighted sourcing of freshwater runoff from Pacific-draining continental and coastal basins in south-western Patagonia (41-56° S): characterizing regional inputs to Chilean fjords - Paulo Moreno-Meynard; Osvaldo Artal; Rodrigo Torres; Brian Reid (Frontiers in Marine Science, 2024)
Global estimates of the supply of dissolved and suspended materials to the ocean, in order to be relevant at either political or ecological scales, belie a finer-scale analysis necessary for understanding specific terrestrial-marine interactions. This is especially true for continental runoff to the marine critical zone of inland fjords and channels, where mechanisms, drivers, and predictions need to be elaborated in the context of changing land use and shifting climate forcing. In fjords in south-western Patagonia, runoff from small coastal and large continental basins (~310 x10 3 km 2 ), sourced from a diverse geography and wide climatic gradient (<150 – 6,000+ mm/year), correspond with a very low density of hydrological and water quality observations. Based on the recently developed regional runoff model (FLOW), we estimated the coastal freshwater discharges and characterized flow-weighted sourcing (land use-cover type, climate, glaciers/geology, and soil province) for Pacific drainages from 41° to 56° south latitude. An estimated 692 km 3 /year (mean across 1979-2018), or 2% of worldwide total, is more than 85% of previous estimates for the much larger Pacific South American input. Based on limited water quality observations and inference from runoff sourcing, we predict general patterns of export for four groups of continental resources important for marine productivity, including: significant regional variation in flow seasonality, a N-S gradient in declining input of silicic acid and increased glacial input of sediment and iron, and potential shift in dissolved organic matter input sources from rainforest (potentially labile) to peatlands (refractory). Finally, we emphasize the temporal and spatial consequences of near-reference condition river runoff for marine ecosystem productivity and function in the Patagonian fjords, with specific recommendations for water quality standards and sustained monitoring for coupled river and marine ecosystems.

Production and anti-inflammatory and analgesic effects of sphaeralgin from transformed and non-transformed cells in suspension cultures of Sphaeralcea angustifolia (Cav.) G. Don - Rogelio Reyes-Pérez; Pilar Nicasio-Torres; Manasés González-Cortazar; José de Jesús Arellano-Garcia; Rosa Mariana Montiel-Ruiz; Rodrigo Vargas-Ruiz; Ma. Dolores Pérez-García; Juanita Pérez-Hernández (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Enriched Environment Contributes to the Recovery from Neurotoxin-Induced Parkinson’s Disease Pathology - Daphne Alcalá-Zúniga; Erika Espinoza-Torres; Ranjit Kumar Das; Magaly Vargas; Oscar Maldonado; Omar Benavides; Arvind Manojkumar; Roberto de la Garza; Natalia Davila; Isaac Perez; Alejandro Hernandez Martinez; Deepa Roy; et al. (Molecular Neurobiology, 2024)
Parkinson’s disease (PD) is a neurological disorder that affects dopaminergic neurons. The lack of understanding of the underlying molecular mechanisms of PD pathology makes treating it a challenge. Several pieces of evidence support the protective role of enriched environment (EE) and exercise on dopaminergic neurons. The specific aspect(s) of neuroprotection after exposure to EE have not been identified. Therefore, we have investigated the protective role of EE on dopamine dysregulation and subsequent downregulation of DJ1 protein using in vitro and in vivo models of PD. Our study for the first time demonstrated that DJ1 expression has a direct correlation with dopamine downregulation in PD models and exposure to EE has a significant impact on improving the behavioral changes in PD mice. This research provides evidence that exercise in EE has a positive effect on PD without interfering with the current line of therapy.

Mixed-marker data indicate the population biology, history, and the stock structure of crevalle jack Caranx hippos (Linnaeus, 1766) in the tropical Atlantic: A regional and latitudinal conservation genetics approach - Maria Clara G. Queiroz-Brito; Gabriela Rocha Defavari; Uedson Pereira Jacobina; Rodrigo A. Torres (Regional Studies in Marine Science, 2024)

Performance, nutrient utilization and meat quality traits in Bos indicus cattle: a meta-analysis examining the effect of residual feed intake - Daniela A. Vesga; Rodrigo N. S. Torres; José B. S. Moreira; Yury T. Granja-Salcedo; Otavio R. Machado Neto; Luis Artur L. Chardulo; Mahesh N. Nair; Pedro H. V. Carvalho; Welder A. Baldassini (Tropical Animal Health and Production, 2024)

Feline leishmaniasis in an animal shelter in northeastern Brazil: Clinical aspects, coinfections, molecular detection, and serological study of a new recombinant protein - Luiz Fernando de Jesus Nascimento; Ana Carolina Amado-Gomes; Filipe Dantas-Torres; Fred Luciano Neves Santos; Wemerson de Santana Neres; Pedro Estevão de Souza Filho; Mariana Tibúrcio Santos; José Rodrigo Santos Silva; Cláudia Fideles Resende; Jenner Karlisson Pimenta dos Reis; Sona Jain; João Luís Reis Cunha; et al. (Research in Veterinary Science, 2024)

MANGLEE: A Tool for Mapping and Monitoring MANgrove Ecosystem on Google Earth Engine—A Case Study in Ecuador - Lorena Caiza-Morales; Cristina Gómez; Rodrigo Torres; Andrea Puzzi Nicolau; José Miguel Olano (Journal of Geovisualization and Spatial Analysis, 2024)
Mangroves, integral to ecological balance and socioeconomic well-being, are facing a concerning decline worldwide. Remote sensing is essential for monitoring their evolution, yet its effectiveness is hindered in developing countries by economic and technical constraints. In addressing this issue, this paper introduces MANGLEE (Mangrove Mapping and Monitoring Tool in Google Earth Engine), an accessible, adaptable, and multipurpose tool designed to address the challenges associated with sustainable mangrove management. Leveraging remote sensing data, machine learning techniques (Random Forest), and change detection methods, MANGLEE consists of three independent modules. The first module acquires, processes, and calculates indices of optical and Synthetic Aperture Radar (SAR) data, enhancing tracking capabilities in the presence of atmospheric interferences. The second module employs Random Forest to classify mangrove and non-mangrove areas, providing accurate binary maps. The third module identifies changes between two-time mangrove maps, categorizing alterations as losses or gains. To validate MANGLEE’s effectiveness, we conducted a case study in the mangroves of Guayas, Ecuador, a region historically threatened by shrimp farming. Utilizing data from 2018 to 2022, our findings reveal a significant loss of over 2900 hectares, with 46% occurring in legally protected areas. This loss corresponds to the rapid expansion of Ecuador’s shrimp industry, confirming the tool’s efficacy in monitoring mangroves despite cloud cover challenges. MANGLEE demonstrates its potential as a valuable tool for mangrove monitoring, offering insights essential for conservation, management plans, and decision-making processes. Remarkably, it facilitates equal access and the optimal utilization of resources, contributing significantly to the preservation of coastal ecosystems.

Potential of different strategies to increase intramuscular fat deposition in sheep: A meta-analysis study - Rodrigo de Nazaré Santos Torres; Caren Paludo Ghedini; Luis Artur Loyola Chardulo; Welder Angelo Baldassini; Rogério Abdallah Curi; Guilherme Luis Pereira; Jon Patrick Schoonmaker; Marco Tulio Costa Almeida; Ciniro Costa; Otavio Rodrigues Machado Neto (Small Ruminant Research, 2024)

Association parameters for Cubic-Plus-Association equation of state determined by molecular dynamics and Petroleomics: Prediction of asphaltene precipitation - Ivan Moncayo-Riascos; Juan David Aristizábal; Oscar Ramírez-Jaramillo; Fernando A. Rojas-Ruiz; Jorge A. Orrego-Ruiz; Rodrigo Torres-Sáez; Cristiam Cundar; Wilson Cañas-Marín; Raul Osorio (Fuel, 2024)

Social-ecological vulnerability to environmental extremes and adaptation pathways in small-scale fisheries of the southern California Current - Fiorenza Micheli; Andrea Saenz-Arroyo; Emilius Aalto; Rodrigo Beas-Luna; Charles A. Boch; Juan Camilo Cardenas; Giulio A. De Leo; Eduardo Diaz; Antonio Espinoza-Montes; Elena Finkbeiner; Jan Freiwald; Stuart Fulton; et al. (Frontiers in Marine Science, 2024)
Coastal ecosystems and human communities are threatened worldwide by climate change, and shocks from social, market and political change. There is an urgent global need to promote resilient food production and livelihoods in the face of these shocks. Small-scale fisheries (SSF) in rural settings can be particularly vulnerable as they frequently lack the resources, rights and infrastructure to respond to shocks originating outside the focal systems. We examined ecological and social outcomes of environmental extremes in a SSF socio-ecological system (SES) by using long-term oceanographic (between 2010-2019) and ecological (2006-2018) data tracking change in a kelp forest ecosystem of Baja California, Mexico, and concurrent documentation of proactive and reactive actions of a fishing community organized in a cooperative. Results indicate a complex landscape of ‘winners’ and ‘losers’ among species and fisheries exposed to unprecedented environmental extremes, including marine heat waves and prolonged hypoxia, and a suite of adaptive actions by the local fishing cooperative, and others in the region, that have helped confront these rapid and drastic changes. Cooperatives have established voluntary marine reserves to promote recovery of affected populations and have invested in diversification of activities enabled by access rights, collective decision-making, and participatory science programs. Results indicate that local actions can support social and ecological resilience in the face of shocks, and that enabling locally-driven adaptation pathways is critical to resilience. This case study highlights the crucial importance of strengthening and supporting rights, governance, capacity, flexibility, learning, and agency for coastal communities to respond to change and sustain their livelihoods and ecosystems in the long run.

Depuration of landfill leachates using fly ash as a catalyst in solar advanced oxidation processes and a compost bioreactor - Rodrigo Poblete; Flavio Alanís; Efraím A. Serna-Galvis; Ricardo A. Torres-Palma (Journal of Environmental Chemical Engineering, 2024)

Multispecies genetic approach reveals divergent connectivity patterns in marine fish from Western Atlantic - Daniele de Jesus Gama-Maia; Leonardo Luiz Calado; Jamille de Araujo Bitencourt; Paulo Roberto Antunes de Mello Affonso; Gustavo Souza; Rodrigo Augusto Torres; Uedson Pereira Jacobina (Marine Biodiversity, 2024)

Strategies of virginiamycin supplementation in the postweaning phase on growth performance and carcass quality of beef cattle - Rodrigo da Costa Gomes; Gilberto Romeiro de Oliveira Menezes; Ricardo Favero; Ricardo Kazama; Georg Altrak; Ivone Yurika Mizubuti; Marina de Nadai Bonin Gomes; Gelson Luis Dias Feijó; Denise Baptaglin Montagner; Thiago Luís Alves Campos de Araújo; Dorgival Morais de Lima Júnior; Roberto Augusto de Almeida Torres Júnior; et al. (Tropical Animal Health and Production, 2024)

Seismic behaviour of reinforced-masonry aggregate under different types of interaction between adjacent dwellings - Sebastian Torres-Olivares; Beatriz González-Rodrigo; Erick I. Saavedra-Flores; Juan Carlos Mosquera-Feijoo (Bulletin of Earthquake Engineering, 2024)
Assessing the seismic vulnerability of existing buildings is an essential task for the management of earthquake disasters. For this purpose, the seismic behaviour of buildings is usually determined under the assumption of isolated conditions, although aggregate structures are one of the most common typologies found in urban centres. This study aims to investigate the nonlinear static behaviour of aggregate dwellings consisting of grouted reinforced concrete block configurations commonly observed in San José, Costa Rica. This research investigates the use of several strategies to model connections between adjacent buildings which are typically found in modern building practises in this country. The methodology used here to analyse the seismic behaviour of isolated and row-aggregated dwellings reveals significant differences in their response under seismic loads, especially when acting perpendicular to the aggregate. The study reveals that the type of interaction considered between adjacent buildings has a very important impact on the seismic capacity and failure mechanisms of the aggregated structures. This procedure can also be applied to the vulnerability assessment and retrofit of existing aggregates.

Assessment of lamb meat quality in two cooking methods: Water bath versus oven cooking - Mariana da S. Leal; Welder A. Baldassini; Rodrigo de N.S. Torres; Rogério A. Curi; Guilherme L. Pereira; Luis Artur L. Chardulo; Rafael F. Santos; Paulo R.L. Meirelles; Ciniro Costa (Small Ruminant Research, 2023)

Restricted connectivity for cobia Rachycentron canadum (Perciformes: Rachycentridae) in the Western Atlantic Ocean - Maria Raquel M. Coimbra; Emilly Benevides; Renata da Silva Farias; Bruno C. N. R. da Silva; Sara Cloux; Vicente Pérez‐Muñuzuri; Manuel Vera; Rodrigo Torres (Fisheries Oceanography, 2023)
Cobia ( Rachycentron canadum ) is a coastal pelagic migratory fish species of tropical and subtropical waters, where it is an important game fish and it has been commercially expanded in offshore aquaculture systems. Understanding population connectivity is of utmost importance to the sustainable use and conservation of aquatic resources, and information on genetic diversity and structure is key element in unraveling differentiation when no clear physical barriers exist. In the present study, cobia genetic diversity and structure were depicted using mitochondrial DNA cytochrome b sequencing and microsatellite genotyping in samples from the Southwestern Atlantic and showed that a major single population inhabits the southern hemisphere. Cytochrome b sequencing also suggested that the Indian Ocean is the center of origin for this species' diversification. A hierarchical analysis of AMOVA compared sampling locations from the Northwestern Atlantic (from a previous study) with the Southwestern ones using nine shared microsatellite markers. Differentiation among groups (F CT = 0.41), Bayesian clustering analysis, and complementary ordination analyses (by discriminant analysis of principal components [DAPC] and factorial correspondence analysis [3D‐FCA]) presented a clear separation between the two hemispheres, supported by a Lagrangian model that explained the ocean dynamics over larval retention on the Western Atlantic. Another genetic subgroup intermingled with the main Southwestern group may also exist further south, probably associated with the Vitória‐Trindade Ridge and the local current systems. The distribution of this species in metapopulations is of extreme relevance for fisheries and fish hatcheries management in the Atlantic Ocean.

Direct and indirect impacts of ocean acidification and warming on algae-herbivore interactions in intertidal habitats - Samanta Benítez; Jorge M. Navarro; Daniela Mardones; Paola A. Villanueva; Felipe Ramirez-Kushel; Rodrigo Torres; Nelson A. Lagos (Marine Pollution Bulletin, 2023)

Two-step valorization of invasive species Rosa rubiginosa L. husk waste through eco-friendly optimized pectin extraction and subsequent pyrolysis - Rodrigo Torres-Sciancalepore; Mathias Riveros-Gomez; Daniela Zalazar-García; Daniela Asensio; María Paula Fabani; Rosa Rodriguez; Gastón Fouga; Germán Mazza (Journal of Environmental Chemical Engineering, 2023)

Unlocking the antioxidant and antimicrobial potential of flavone and amide-rich fractions from Conchocarpus macrocarpus (Rutaceae) leaves - Elielson Rodrigo Silveira; Priscila Bezerra Torres; Katia Castanho Scortecci; Hugo Alexandre Oliveira Rocha; Ivana Barbosa Suffredini; Jefferson de Souza Silva; Déborah Yara Alves Cursino dos Santos (Brazilian Journal of Botany, 2023)

Muscle proteome of crossbred cattle that received vitamin A at birth: impacts on meat quality traits - Rayssa S. Scapol; Welder A. Baldassini; Mohammed Gagaoua; Germán D. Ramírez-Zamudio; Márcio M. Ladeira; Mirele D. Poleti; José Bento S. Ferraz; Rodrigo de N.S. Torres; Juliana A. Torrecilhas; Guilherme L. Pereira; Otavio R. Machado-Neto; Rogério A. Curi; et al. (Livestock Science, 2023)

Calibration of a Three-dimensional Slope Stability Evaluation in Brazilian iron Open Pit Mine - Vidal Félix Navarro Torres; Rodrigo Dockendorff; Juan Manuel Girao Sotomayor; Cristian Castro; Aristotelina Ferreira da Silva (Geotechnical and Geological Engineering, 2023)

Late Cretaceous calcareous nannofossil assemblages from Colombia: Biostratigraphic contributions to northwestern South American Basins - Estefanía Angulo-Pardo; Felipe Vallejo-Hincapié; Rodrigo Do Monte Guerra; Andrés Pardo-Trujillo; Carlos A. Giraldo-Villegas; Jenny García González; Sebastian Hernández Duran; Sergio Herrera Quijano; Angelo Plata Torres; Raúl Trejos-Tamayo (Journal of South American Earth Sciences, 2023)

Comparative genomic damage among three shark species with different habits: Sublethal impacts of human origin in a protected island environment in the South Atlantic - Camila Araújo; Pedro Carneiro; Leonardo Fidelis; Bruna Nascimento; Marina Antunes; Danielle Viana; Paulo Oliveira; Rodrigo Torres; Fábio Hazin; Mônica Adam (Marine Pollution Bulletin, 2023)

Iron and silicic acid addition effects on early spring macronutrient drawdown and biogenic silica production of Patagonia estuarine waters - Rodrigo Torres; Rob Sherrell; Brian Reid; Gemita Pizarro; Máximo Frangópulos; Emilio Alarcón; Magdalena Márquez; Francisco Díaz-Rosas; Eduardo Menschel; Humberto E. González; Paulo Moreno-Meynard; Paulina Montero; et al. (Progress in Oceanography, 2023)

Effects of molasses supplementation on animal performance and carcass parameters of beef cattle: a meta-analysis - Rodrigo de Nazaré Santos Torres; João Pedro Amaral Bertoco; Maria Carolina Gonçalves de Arruda; Larissa de Melo Coelho; Josimari Regina Paschoaloto; Otavio Rodrigues Machado Neto; Jane Maria Bertocco Ezequiel; Marco Túlio Costa Almeida; Luis Artur Loyola Chardulo; Welder Angelo Baldassini (Tropical Animal Health and Production, 2023)

Study of a light hydrocarbon fraction spill migration that occurred in an area of the Mexican southeast using computational fluid dynamics - Miguel Ángel Arellano-González; Pedro López-Ordaz; Dulce María Palmerín-Carreño; Jorge Gracida-Rodríguez; María Belem Arce-Vázquez; Analiz Mondragón-Cisneros; Rodrigo Melgarejo-Torres (Environmental Science and Pollution Research, 2023)

Novel clinical and immunological features associated with persistent post-acute sequelae of COVID-19 after six months of follow-up: a pilot study - Jiram Torres-Ruiz; Julieta Lomelín-Gascón; Jaquelin Lira Luna; Ana Sofia Vargas- Castro; Alfredo Pérez-Fragoso; Miroslava Nuñez-Aguirre; Beatriz Alcalá-Carmona; Abdiel Absalón-Aguilar; Jennifer T. Balderas-Miranda; José Luis Maravillas-Montero; Nancy R. Mejía-Domínguez; Carlos Núñez-Álvarez; et al. (Infectious Diseases, 2023)

Distribution of dinoflagellate cyst assemblages in surface sediments of Magellan fjords and channels (Patagonia, Chile) with a focus on harmful species: An overview on environmental scenario - Pablo Salgado; Gemita Pizarro; Máximo Frangopulos; Marco Pinto-Torres; Carolina Toro; Rodrigo Torres; Emilio Alarcón; Leonardo Guzmán; Karen Manríquez; Roberto Raimapo; Emma Cascales (Progress in Oceanography, 2023)

Estimation of body weight using body measurements in female water buffaloes reared in southeastern Mexico - Jorge Ruiz-Ramos; Oswaldo M. Torres-Chable; Jorge A. Peralta-Torres; Nadia F. Ojeda-Robertos; Carlos Luna-Palomera; Rodrigo Portillo-Salgado; Thobela Louis Tyasi; Antonio Leandro Chaves Gurgel; Luís Carlos Vinhas Ítavo; Alfonso J. Chay-Canul (Tropical Animal Health and Production, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Pineapple mealybug wilt-associated viruses 1, 2, and 3 are associated with mealybug wilt disease of pineapple in Peru - Emerson Clovis Carrasco-Lozano; Gabriela Angela Carrillo-Ordóñez; Delia Gamarra-Gamarra; Gilberto Torres-Suarez; Charo Milagros Villar; Claudia Stange; Rodrigo A. Valverde (Journal of Plant Pathology, 2023)
Mealybug wilt of pineapple (MWP) is the most important disease of pineapple worldwide. During the months of September and November 2020, pineapple production fields of the cultivar Hawaiiana and hybrid MD-2 in Satipo and Chanchamayo provinces of Peru, showed typical symptoms of MWP. Based on symptoms, the disease incidence level ranged between 70 and 90%. Symptomatic and asymptomatic foliar samples were collected and tested by RT-PCR using primers specific for pineapple mealybug wilt virus (PMWaV) 1, 2, and 3. Selected amplified fragments were sequenced and analyzed with bioinformatics tools. PMWaV-1, 2, and 3 were detected in symptomatic samples of both cultivars but not in asymptomatic samples. PMWaV-1 showed a nucleotide identity of 91.70% with PMWaV-1 from Thailand; PMWaV-2, 99.81% with PMWaV-2 from Thailand; and PMWaV-3, 99.09% with PMWaV-3 from Cuba. Mixed infections of PMWaV-1, 2, and 3 were also detected in both cultivars. To our knowledge, this is the first report of PMWaV-1, 2, and 3, associated with pineapple in Peru.

Potential of nutritional strategies to reduce enteric methane emission in feedlot sheep: A meta-analysis and multivariate analysis - Rodrigo de Nazaré Santos Torres; Larissa de Melo Coelho; Caren Paludo Ghedini; Otavio Rodrigues Machado Neto; Luis Artur Loyola Chardulo; Juliana Akamine Torrecilhas; Roberta de Lima Valença; Welder Angelo Baldassini; Marco Tulio Costa Almeida (Small Ruminant Research, 2023)

Coconut water-based extender for seminal preservation in small ruminants: A meta-analysis study - Rogério Amorim dos Reis; Rodrigo de Nazaré Santos Torres; Iara Magalhães Ribeiro; Ciro Alexandre Alves Torres; Bruna Waddington de Freitas (Small Ruminant Research, 2023)

Antarctica Slope Front bifurcation eddy: A stationary feature influencing CO2 dynamics in the northern Antarctic Peninsula - Brendon Yuri Damini; Raul Rodrigo Costa; Tiago S. Dotto; Carlos Rafael Borges Mendes; Juan Camilo Torres-Lasso; Marina do V.C. Azaneu; Mauricio M. Mata; Rodrigo Kerr (Progress in Oceanography, 2023)

Combined effects of climate change stressors and predators with contrasting feeding-digestion strategies on a mussel species - Patricio H. Manríquez; Claudio P. González; María Elisa Jara; Sue-Ann Watson; Rodrigo Torres; Paolo Domenici; Cristian Duarte (Marine Pollution Bulletin, 2023)

Skeletal muscle gene expression and meat quality of F1 Angus–Nellore young steers and bulls feedlot finished - Bismarck M. Santiago; Welder A. Baldassini; Marcos R. Chiaratti; Anand K. Pandey; Juliana A. Torrecilhas; Rodrigo N.S. Torres; Richard V. Ribeiro; Dante P.D. Lanna; Guilherme L. Pereira; Rogério A. Curi; Luis Artur L. Chardulo; Otávio R. Machado Neto (Livestock Science, 2023)

Ocean acidification and seasonal temperature extremes combine to impair the thermal physiology of a sub-Antarctic fish - María E. Lattuca; Fabián A. Vanella; Gabriela Malanga; Maximiliano D. Rubel; Patricio H. Manríquez; Rodrigo Torres; Katharina Alter; Stefano Marras; Myron A. Peck; Paolo Domenici; Daniel A. Fernández (Science of The Total Environment, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Models to predict live weight from heart girth in crossbred beef heifers - Denis R. Chico-Alcudia; Rodrigo Portillo-Salgado; Enrique Camacho-Pérez; Jorge A. Peralta-Torres; Juan C. Angeles-Hernandez; Alfonso L. Muñoz-Benitez; Víctor Hugo Severino Lendechy; Antonio Leandro Chaves Gurgel; Gelson dos Santos Difante; Luís Carlos Vinhas Ítavo; Alfonso J. Chay-Canul (Tropical Animal Health and Production, 2022)

Using a social-ecological systems perspective to identify context specific actions to build resilience in small scale fisheries in Mexico - Carmen Valdez-Rojas; Rodrigo Beas-Luna; Julio Lorda; José A. Zepeda-Domínguez; Gabriela Montáño-Moctezuma; Alfonso Medellín-Ortíz; Jorge Torre; Fiorenza Micheli (Frontiers in Marine Science, 2022)
To promote the resilience and sustainability of coastal social-ecological systems (SES), it is necessary to implement adaptive and participatory management schemes. Successful examples of adaptation to the rapid change in coastal SES exist, but the question of whether these cases may be scalable to other regions and contexts remains. To this end, the present study aimed to identify how successful management strategies implemented in a fishing cooperative in Baja California, Mexico, can be adapted to other coastal SES. In particular, this study aimed to understand whether adaptive co-management of Isla Natividad (IN) could be replicated in Isla Todos Santos (ITS), a biophysically similar coastal SES to IN but with different results with regard to fisheries management. We found that the resource systems and resources in both SESs were similar. However, there were substantial differences with regard to governance and resource users. In Isla Natividad, the level of organization orchestrated by the resource users has contributed to establishing rules and sanctions that have supported the sustainable use of fishery resources. On the contrary, in ITS, the number of resource users and their socioeconomic attributes have impeded the establishment of effective rules or sanctions. The results of this study suggest that the ITS governance system needs to be improved in order to adapt some of the IN management strategies to increase its adaptive capacity. To promote successful adaptive management, it is necessary to develop context-specific adaptive pathways that contribute to greater resilience in the SESs of this region and in other regions that face similar conditions.

Performance of Sentinel-2 SAFER ET model for daily and seasonal estimation of grapevine water consumption - Anderson L. S. Safre; Ayman Nassar; Alfonso Torres-Rua; Mayhar Aboutalebi; João C. C. Saad; Rodrigo L. Manzione; Antonio Heriberto de Castro Teixeira; John H. Prueger; Lynn G. McKee; Joseph G. Alfieri; Lawrence E. Hipps; Hector Nieto; et al. (Irrigation Science, 2022)

Understanding the Implications of Hydrographic Processes on the Dynamics of the Carbonate System in a Sub-Antarctic Marine-Terminating Glacier-Fjord (53°S) - Jurleys P. Vellojin; Gonzalo S. Saldías; Susan E. Allen; Rodrigo Torres; Maximiliano Vergara-Jara; Marcus Sobarzo; Michael D. DeGrandpre; José Luis Iriarte (Frontiers in Marine Science, 2022)
The biogeochemical dynamics of fjords in the southeastern Pacific Ocean are strongly influenced by hydrological and oceanographic processes occurring at a seasonal scale. In this study, we describe the role of hydrographic forcing on the seasonal variability of the carbonate system of the Sub-Antarctic glacial fjord, Seno Ballena, in the Strait of Magellan (53°S). Biogeochemical variables were measured in 2018 during three seasonal hydrographic cruises (fall, winter and spring) and from a high-frequency p CO 2 -pH mooring for 10 months at 10 ± 1 m depth in the fjord. The hydrographic data showed that freshwater input from the glacier influenced the adjacent surface layer of the fjord and forced the development of undersaturated CO 2 (< 400 μatm) and low aragonite saturation state (Ω Ar < 1) water. During spring, the surface water had relatively low p CO 2 (mean = 365, range: 167 - 471 μatm), high pH (mean = 8.1 on the total proton concentration scale, range: 8.0 - 8.3), and high Ω Ar (mean = 1.6, range: 1.3 - 4.0). Concurrent measurements of phytoplankton biomass and nutrient conditions during spring indicated that the periods of lower p CO 2 values corresponded to higher phytoplankton photosynthesis rates, resulting from autochthonous nutrient input and vertical mixing. In contrast, higher values of p CO 2 (range: 365 – 433 μatm) and relatively lower values of pH T (range: 8.0 – 8.1) and Ω Ar (range: 0.9 – 2.0) were recorded in cold surface waters during winter and fall. The naturally low freshwater carbonate ion concentrations diluted the carbonate ion concentrations in seawater and decreased the calcium carbonate saturation of the fjord. In spring, at 10 m depth, higher primary productivity caused a relative increase in Ω Ar and pH T . Assuming global climate change will bring further glacier retreat and ocean acidification, this study represents important advances in our understanding of glacier meltwater processes on CO 2 dynamics in glacier–fjord systems.

Thallium Differentially Affects Macronutrients Concentration and Stoichiometric Ratios with Nitrogen in the Leaves of Chili Pepper Varieties - María de la Luz Buendía-Valverde; Fernando C. Gómez-Merino; Tarsicio Corona-Torres; Serafín Cruz-Izquierdo; Rodrigo A. Mateos-Nava; Libia I. Trejo-Téllez (Water, Air, & Soil Pollution, 2022)

Mapping Potential Toxic Elements in Agricultural and Natural Soils of the Piedemonte Llanero in Colombia - Juan Manuel Trujillo-González; Marco Aurelio Torres-Mora; Marlon Serrano-Gómez; Edgar Fernando Castillo-Monroy; Raimundo Jiménez Ballesta; Jesús Rodrigo-Comino (Water, Air, & Soil Pollution, 2022)

Microclimate and animal thermal comfort indexes in different silvopastoral system arrangements in Caatinga - Clemente Fernandes dos Santos Neto; Rodrigo Gregório da Silva; Samuel Rocha Maranhão; Antônia Flávia Fernandes Torres; José Antonio Delfino Barbosa Filho; Vitor Hugo Maués Macedo; Magno José Duarte Cândido (International Journal of Biometeorology, 2022)

Hydrofracturing in situ stress measurements of itabirite in the Brazilian Ferriferous Quadrangle and their limitations - Henrique de Andrade Penido; Rodrigo Peluci de Figueiredo; André Pacheco de Assis; Vidal Félix Navarro Torres; Juan Manuel Girao Sotomayor; Alessandro Guimarães (Geotechnical and Geological Engineering, 2022)

Role of the YehD fimbriae in the virulence‐associated properties of enteroaggregative Escherichia coli - Jorge Soria‐Bustos; Waleska Saitz; Abraham Medrano; Cristina Lara‐Ochoa; Zineb Bennis; Valerio Monteiro‐Neto; Camilla Itapary dos Santos; Josias Rodrigues; Rodrigo T. Hernandes; Jorge A. Yáñez; Javier Torres; Fernando Navarro‐García; et al. (Environmental Microbiology, 2022)
Summary The interaction of enteroaggregative Escherichia coli (EAEC) strains with the colonic gut mucosa is characterized by the ability of the bacteria to form robust biofilms, to bind mucin, and induce a local inflammatory response. These events are mediated by a repertoire of five different aggregative adherence fimbriae variants (AAF/I‐V) typically encoded on virulence plasmids. In this study, we report the production in EAEC strains of a new Y eh D f imbriae (YDF), which is encoded by the chromosomal gene cluster yehABCD , also present in most E. coli strains. Immuno‐labelling of EAEC strain 042 with anti‐AAF/II and anti‐YDF antibodies demonstrated the presence of both AAF/II and YDF on the bacterial surface. We investigated the role of YDF in cell adherence, biofilm formation, colonization of spinach leaves, and induction of pro‐inflammatory cytokines release. To this aim, we constructed yehD deletion mutants in different EAEC backgrounds (strains 17‐2, 042, 55989, C1010, 278‐1, J7) each harbouring one of the five AAFs. The effect of the YDF mutation was strain dependent and AAF independent as the lack of YDF had a different impact on the phenotypes manifested by the different EAECs tested. Expression of the yehABCD operon in a E. coli K12 ORN172 showed that YDF is important for biofilm formation but not for adherence to HeLa cells. Lastly, screening of pro‐inflammatory cytokines in supernatants of Caco‐2 cells infected with EAEC strains 042 and J7 and their isogenic Δ yehD mutants showed that these mutants were significantly defective in release of IL‐8 and TNF‐α. This study contributes to the understanding of the complex and diverse mechanisms of adherence of EAEC strains and identifies a new potential target for preventive measures of gastrointestinal illness caused by EAEC and other E. coli pathogroups.

Severity of SARS-CoV-2 infection is linked to double-negative (CD27− IgD−) B cell subset numbers - Rodrigo Cervantes-Díaz; Víctor Andrés Sosa-Hernández; Jiram Torres-Ruíz; Sandra Romero-Ramírez; Mariana Cañez-Hernández; Alfredo Pérez-Fragoso; José C. Páez-Franco; David E. Meza-Sánchez; Miriam Pescador-Rojas; Víctor Adrián Sosa-Hernández; Diana Gómez-Martín; José L. Maravillas-Montero (Inflammation Research, 2022)

Effect of trans -cinnamic acid and p -coumaric acid on fibroblast motility: a pilot comparative study of in silico lipophilicity measure - Rodrigo da Silva Viana; Fernanda Lima Torres de Aquino; Emiliano Barreto (Natural Product Research, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

A multi-technique tomography-based approach for non-invasive characterization of additive manufacturing components in view of vacuum/UHV applications: preliminary results - Francesco Grazzi; Carlo Cialdai; Marco Manetti; Mirko Massi; Maria Pia Morigi; Matteo Bettuzzi; Rosa Brancaccio; Fauzia Albertin; Takenao Shinohara; Tetsuya Kai; Anna Fedrigo; Adriano Di Giovanni; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)
In this paper, we have studied an additively manufactured metallic component, intended for ultra-high vacuum application, the exit-snout of the MACHINA transportable proton accelerator beam-line. Metal additive manufacturing components can exhibit heterogeneous and anisotropic microstructures. Two non-destructive imaging techniques, X-ray computed tomography and Neutron Tomography, were employed to examine its microstructure. They unveiled the presence of porosity and channels, the size and composition of grains and intergranular precipitates, and the general behavior of the spatial distribution of the solidification lines. While X-ray computed tomography evidenced qualitative details about the surface roughness and internal defects, neutron tomography showed excellent ability in imaging the spatial density distribution within the component. The anisotropy of the density was attributed to the material building orientation during the 3D printing process. Density variations suggest the possibility of defect pathways, which could affect high vacuum performances. In addition, these results highlight the importance of considering building orientation in the design for additive manufacturing for UHV applications. Graphical Abstract

Transcriptional Profiles Reveal Deregulation of Lipid Metabolism and Inflammatory Pathways in Neurons Exposed to Palmitic Acid - M. Flores-León; N. Alcaraz; M. Pérez-Domínguez; K. Torres-Arciga; R. Rebollar-Vega; I. A. De la Rosa-Velázquez; C. Arriaga-Canon; L. A. Herrera; Clorinda Arias; Rodrigo González-Barrios (Molecular Neurobiology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

High-intensity exercise training induces mitonuclear imbalance and activates the mitochondrial unfolded protein response in the skeletal muscle of aged mice - André Victor Cordeiro; Guilherme Francisco Peruca; Renata Rosseto Braga; Rafael Santos Brícola; Luciene Lenhare; Vagner Ramon Rodrigues Silva; Chadi Pellegrini Anaruma; Carlos Kiyoshi Katashima; Barbara Moreira Crisol; Lucas Torres Barbosa; Fernando Moreira Simabuco; Adelino Sanchez Ramos da Silva; et al. (GeroScience, 2021)

Simple and safe approach for molecular identification of the endangered species Epinephelus itajara - Yrlano Oliveira; Roberto Alencar; Yrlan Oliveira; Rodrigo A. Torres; Iracilda Sampaio; Marcelo Vallinoto; Gláucia C. Silva-Oliveira (Conservation Genetics Resources, 2021)

Spatiotemporal Precipitation Estimation from Rain Gauges and Meteorological Radar Using Geostatistics - Eduardo Cassiraga; J. Jaime Gómez-Hernández; Marc Berenguer; Daniel Sempere-Torres; Javier Rodrigo-Ilarri (Mathematical Geosciences, 2021)

Evaluation of diagnostic accuracy of 10 serological assays for detection of SARS-CoV-2 antibodies - Ainhoa Gutiérrez-Cobos; Sara Gómez de Frutos; Diego Domingo García; Eva Navarro Lara; Ayla Yarci Carrión; Leticia Fontán García-Rodrigo; Arturo Manuel Fraile Torres; Laura Cardeñoso Domingo (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

A mosaic of phytoplankton responses across Patagonia, the southeast Pacific and the southwest Atlantic to ash deposition and trace metal release from the Calbuco volcanic eruption in 2015 - Maximiliano J. Vergara-Jara; Mark J. Hopwood; Thomas J. Browning; Insa Rapp; Rodrigo Torres; Brian Reid; Eric P. Achterberg; José Luis Iriarte (Ocean Science, 2021)
Following the eruption of the Calbuco volcano in April 2015, an extensive ash plume spread across northern Patagonia and into the southeast Pacific and southwest Atlantic oceans. Here, we report on field surveys conducted in the coastal region receiving the highest ash load following the eruption (Reloncaví Fjord). The fortuitous location of a long-term monitoring station in Reloncaví Fjord provided data to evaluate inshore phytoplankton bloom dynamics and carbonate chemistry during April–May 2015. Satellite-derived chlorophyll a measurements over the ocean regions affected by the ash plume in May 2015 were obtained to determine the spatial–temporal gradients in the offshore phytoplankton response to ash. Additionally, leaching experiments were performed to quantify the release from ash into solution of total alkalinity, trace elements (dissolved Fe, Mn, Pb, Co, Cu, Ni and Cd) and major ions (F−, Cl−, SO42-, NO3-, Li+, Na+, NH4+, K+, Mg2+ and Ca2+). Within Reloncaví Fjord, integrated peak diatom abundances during the May 2015 austral bloom were approximately 2–4 times higher than usual (up to 1.4 × 1011 cells m−2, integrated to 15 m depth), with the bloom intensity perhaps moderated due to high ash loadings in the 2 weeks following the eruption. Any mechanistic link between ash deposition and the Reloncaví diatom bloom can, however, only be speculated on due to the lack of data immediately preceding and following the eruption. In the offshore southeast Pacific, a short-duration phytoplankton bloom corresponded closely in space and time to the maximum observed ash plume, potentially in response to Fe fertilisation of a region where phytoplankton growth is typically Fe limited at this time of year. Conversely, no clear fertilisation on the same timescale was found in the area subject to an ash plume over the southwest Atlantic where the availability of fixed nitrogen is thought to limit phytoplankton growth. This was consistent with no significant release of fixed nitrogen (NOx or NH4) from Calbuco ash. In addition to the release of nanomolar concentrations of dissolved Fe from ash suspended in seawater, it was observed that low loadings (

Seasonal Changes in Dissolved Organic Matter Composition in a Patagonian Fjord Affected by Glacier Melt Inputs - Matthew G. Marshall; Anne M. Kellerman; Jemma L. Wadham; Jon R. Hawkings; Giovanni Daneri; Rodrigo Torres; Helena V. Pryer; Alexander Beaton; Hong Chin Ng; Alejandra Urra; Laura F. Robinson; Robert G. M. Spencer (Frontiers in Marine Science, 2021)
Biogeochemical processes in fjords are likely affected by changes in surrounding glacier cover but very little is known about how meltwater directly influences dissolved organic matter (DOM) in fjords. Moreover, the data available are restricted to a handful of northern hemisphere sites. Here we analyze seasonal and spatial variation in dissolved organic carbon (DOC) concentration and DOM composition (spectrofluorescence, ultrahigh resolution mass spectrometry) in Baker-Martinez Fjord, Chilean Patagonia (48°S), to infer the impacts of rapid regional deglaciation on fjord DOM. We show that surface layer DOC concentrations do not vary significantly between seasons, but DOM composition is sensitive to differences in riverine inputs. In summer, higher protein-like fluorescence reflects increased glacial meltwater inputs, whilst molecular level data show weaker influence from marine DOM due to more intense stratification. We postulate that the shifting seasonal balance of riverine and marine waters affects the supply of biolabile peptides and organic nitrogen cycling in the surface layer. Trends in DOM composition with increasing salinity are consistent with patterns in estuaries (i.e. preferential removal of aromatic compounds and increasing relative contribution of unsaturated and heteroatom-rich DOM from marine sources). Preliminary estimates also suggest that at least 10% of the annual organic carbon stock in this fjord is supplied by the four largest, glacially fed rivers and that these inputs are dominated by dissolved (84%) over particulate organic carbon. Riverine DOC may therefore be an important carbon subsidy to bacterial communities in the inner fjord. The overall findings highlight the biogeochemical sensitivity of a Patagonian fjord to changes in glacier melt input, which likely has relevance for other glaciated fjords in a warming climate.

Population genetics reveals global and regional history of the apex predator Galeocerdo cuvier (carcharhiniformes) with comments on mitigating shark attacks in north‐eastern brazil - Flávia R.S. Andrade; André S. Afonso; Fábio H.V. Hazin; Fernando F. Mendonça; Rodrigo A. Torres (Marine Ecology, 2021)
The knowledge of the population structure of a given species is of great importance for its conservation and for the management of its fishing exploitation, especially for sharks. The tiger shark ( Galeocerdo cuvier Péron&Lesueur, 1822) is an apex predator species that is currently listed as “Near Threatened” on the International Union for the Conservation of Nature's (IUCN) Red List of Threatened Species. In this study, the tiger shark's genetic structure in the Metropolitan Region of Recife (MRR) and oceanic archipelago of Fernando de Noronha (FN) was investigated based on one mitochondrial and two nuclear DNA markers. In addition, sequenced data from other geographic sites were added into the mitochondrial analysis. The data showed moderate‐to‐high genetic diversity, and it is consistent with good resilience of G. cuvier in ecological terms. The structuring tests reinforced a global distinction of the species in two lineages, one being from the Indo‐Pacific and the other from the North Atlantic. Also, this analysis showed the close relationship between tiger sharks from Indo‐Pacific and South‐eastern coast of Brazil. The Bayesian and AMOVA tests indicated that tiger sharks from FN and MRR are genetically similar, forming a cohesive population. These analyses support live specimen translocations from beaches (where the attacks occur) to distant marine areas given we detected a historical cohesive population occurring between those beaches from MRR and FN Islands where the sharks migrate. This research is the first that has validated individual translocations as a green strategy in South‐western Atlantic.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Top-down characterization of resource use in LCA: from problem definition of resource use to operational characterization factors for dissipation of elements to the environment - Lauran van Oers; Jeroen B. Guinée; Reinout Heijungs; Rita Schulze; Rodrigo A. F. Alvarenga; Jo Dewulf; Johannes Drielsma; David Sanjuan-Delmás; Tobias C. Kampmann; Glenn Bark; Ainara Garcia Uriarte; Pierre Menger; et al. (The International Journal of Life Cycle Assessment, 2020)
Purpose The methods for assessing the impact of using abiotic resources in life cycle assessment (LCA) have always been heavily debated. One of the main reasons for this is the lack of a common understanding of the problem related to resource use. This article reports the results of an effort to reach such common understanding between different stakeholder groups and the LCA community. For this, a top-down approach was applied. Methods To guide the process, a four-level top-down framework was used to (1) demarcate the problem that needs to be assessed, (2) translate this into a modeling concept, (3) derive mathematical equations and fill these with data necessary to calculate the characterization factors, and (4) align the system boundaries and assumptions that are made in the life cycle impact assessment (LCIA) model and the life cycle inventory (LCI) model. Results We started from the following definition of the problem of using resources: the decrease of accessibility on a global level of primary and/or secondary elements over the very long term or short term due to the net result of compromising actions. The system model distinguishes accessible and inaccessible stocks in both the environment and the technosphere. Human actions can compromise the accessible stock through environmental dissipation, technosphere hibernation, and occupation in use or through exploration. As a basis for impact assessment , we propose two parameters: the global change in accessible stock as a net result of the compromising actions and the global amount of the accessible stock. We propose three impact categories for the use of elements: environmental dissipation, technosphere hibernation, and occupation in use, with associated characterization equations for two different time horizons. Finally, preliminary characterization factors are derived and applied in a simple illustrative case study for environmental dissipation. Conclusions Due to data constraints, at this moment, only characterization factors for “dissipation to the environment” over a very-long-term time horizon could be elaborated. The case study shows that the calculation of impact scores might be hampered by insufficient LCI data. Most presently available LCI databases are far from complete in registering the flows necessary to assess the impacts on the accessibility of elements. While applying the framework, various choices are made that could plausibly be made differently. We invite our peers to also use this top-down framework when challenging our choices and elaborate that into a consistent set of choices and assumptions when developing LCIA methods.

(−)-Epicatechin reduces muscle waste after complete spinal cord transection in a murine model: role of ubiquitin–proteasome system - Cristian Gonzalez-Ruiz; Paola Cordero-Anguiano; Axayacatl Morales-Guadarrama; Rodrigo Mondragón-Lozano; Stephanie Sánchez-Torres; Hermelinda Salgado-Ceballos; Francisco Villarreal; Eduardo Meaney; Guillermo Ceballos; Nayelli Nájera (Molecular Biology Reports, 2020)

Climate change effects on turtles of the genus Kinosternon (Testudines: Kinosternidae): an assessment of habitat suitability and climate niche conservatism - Christian Berriozabal-Islas; Aurelio Ramírez-Bautista; Ferdinand Torres-Ángeles; João Fabrício Mota Rodrigues; Rodrigo Macip-Ríos; Pablo Octavio-Aguilar (Hydrobiologia, 2020)

Geographic variation in responses of kelp forest communities of the California Current to recent climatic changes - Rodrigo Beas‐Luna; Fiorenza Micheli; C. Brock Woodson; Mark Carr; Dan Malone; Jorge Torre; Charles Boch; Jennifer E. Caselle; Matt Edwards; Jan Freiwald; Scott L. Hamilton; Arturo Hernandez; et al. (Global Change Biology, 2020)
The changing global climate is having profound effects on coastal marine ecosystems around the world. Structure, functioning, and resilience, however, can vary geographically, depending on species composition, local oceanographic forcing, and other pressures from human activities and use. Understanding ecological responses to environmental change and predicting changes in the structure and functioning of whole ecosystems require large‐scale, long‐term studies, yet most studies trade spatial extent for temporal duration. We address this shortfall by integrating multiple long‐term kelp forest monitoring datasets to evaluate biogeographic patterns and rates of change of key functional groups (FG) along the west coast of North America. Analysis of data from 469 sites spanning Alaska, USA, to Baja California, Mexico, and 373 species (assigned to 18 FG) reveals regional variation in responses to both long‐term (2006–2016) change and a recent marine heatwave (2014–2016) associated with two atmospheric and oceanographic anomalies, the “Blob” and extreme El Niño Southern Oscillation (ENSO). Canopy‐forming kelps appeared most sensitive to warming throughout their range. Other FGs varied in their responses among trophic levels, ecoregions, and in their sensitivity to heatwaves. Changes in community structure were most evident within the southern and northern California ecoregions, while communities in the center of the range were more resilient. We report a poleward shift in abundance of some key FGs. These results reveal major, ongoing region‐wide changes in productive coastal marine ecosystems in response to large‐scale climate variability, and the potential loss of foundation species. In particular, our results suggest that coastal communities that are dependent on kelp forests will be more impacted in the southern portion of the California Current region, highlighting the urgency of implementing adaptive strategies to sustain livelihoods and ensure food security. The results also highlight the value of multiregional integration and coordination of monitoring programs for improving our understanding of marine ecosystems, with the goal of informing policy and resource management in the future.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Pancreatic ductal adenocarcinomas from Mexican patients present a distinct genomic mutational pattern - Paulina Sanchez; Magali Espinosa; Vilma Maldonado; Rodrigo Barquera; Nayeli Belem-Gabiño; Javier Torres; Adrian Cravioto; Jorge Melendez-Zajgla (Molecular Biology Reports, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Cadmium-dependent expression of a new metallothionein identified in Trichomonas vaginalis - Bryan Alexis Netzahualcoyotzi; Jonathan Puente-Rivera; Rodrigo Arreola; Julio César Torres Romero; Maximo Martínez Benitez; Rosalia Lira Carmona; Jorge Antonio Moreno Reyes; Jose de Jesús Olivares Trejo; María Elizbeth Alvarez Sánchez (BioMetals, 2019)

Extreme Marine Heatwaves Alter Kelp Forest Community Near Its Equatorward Distribution Limit - Nur Arafeh-Dalmau; Gabriela Montaño-Moctezuma; José A. Martínez; Rodrigo Beas-Luna; David S. Schoeman; Guillermo Torres-Moye (Frontiers in Marine Science, 2019)

Scaling issues of neutral theory reveal violations of ecological equivalence for dominant Amazonian tree species - Edwin Pos; Juan Ernesto Guevara; Jean‐François Molino; Daniel Sabatier; Olaf S. Bánki; Nigel C.A. Pitman; Hugo F. Mogollón; Roosevelt García‐Villacorta; David Neill; Oliver L. Phillips; Carlos Cerón; Marcos Ríos Paredes; et al. (Ecology Letters, 2019)
Neutral models are often used as null models, testing the relative importance of niche versus neutral processes in shaping diversity. Most versions, however, focus only on regional scale predictions and neglect local level contributions. Recently, a new formulation of spatial neutral theory was published showing an incompatibility between regional and local scale fits where especially the number of rare species was dramatically under‐predicted. Using a forward in time semi‐spatially explicit neutral model and a unique large‐scale Amazonian tree inventory data set, we show that neutral theory not only underestimates the number of rare species but also fails in predicting the excessive dominance of species on both regional and local levels. We show that although there are clear relationships between species composition, spatial and environmental distances, there is also a clear differentiation between species able to attain dominance with and without restriction to specific habitats. We conclude therefore that the apparent dominance of these species is real, and that their excessive abundance can be attributed to fitness differences in different ways, a clear violation of the ecological equivalence assumption of neutral theory.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Increase of Candida antarctica lipase B production under PGK promoter in Pichia pastoris: effect of multicopies - Julia Macedo Robert; Maritza Ocampo Betancur; Antonio Carlos Oliveira Machado; Andrelisse Arruda; Viviane Castelo Branco Reis; Rodrigo Volcan Almeida; Fernando Araripe Gonçalves Torres; Pau Ferrer Alegre; Francisco Valero; Denise Maria Guimarães Freire (Brazilian Journal of Microbiology, 2019)

Chronic Metabolic Derangement-Induced Cognitive Deficits and Neurotoxicity Are Associated with REST Inactivation - Aline Pertile Remor; Rodrigo Augusto da Silva; Filipe José de Matos; Viviane Glaser; Roberta de Paula Martins; Karina Ghisoni; Débora da Luz Scheffer; Denise Carleto Andia; Daniele Portinho; Ana Paula de Souza; Paulo Alexandre de Oliveira; Rui Daniel Prediger; et al. (Molecular Neurobiology, 2019)

Genotypic variation and relationships among traits for root morphology in a panel of tropical maize inbred lines under contrasting nitrogen levels - Lívia Gomes Torres; Diego Gonçalves Caixeta; Wemerson Mendonça Rezende; Andreia Schuster; Camila Ferreira Azevedo; Fabyano Fonseca e Silva; Rodrigo Oliveira DeLima (Euphytica, 2019)

Assessment of acute toxicity and cytotoxicity of fluorescent markers produced by cardanol and glycerol, which are industrial waste, to different biological models - Bruno Ivo Pelizaro; Felipe Camargo Braga; Bruno do Amaral Crispim; Luiz Guilherme Maiolino Lacerda de Barros; Lucas Roberto Pessatto; Edwin José Torres Oliveira; Juliana Miron Vani; Antonio Pancrácio de Souza; Alexeia Barufatti Grisolia; Andréia Conceição Milan Brochado Antoniolli-Silva; Dênis Pires de Lima; Jeandre Augusto dos Santos Jaques; et al. (Environmental Science and Pollution Research, 2019)

Multi-temporal accumulation and risk assessment of available heavy metals in poultry litter fertilized soils from Rio de Janeiro upland region - Cláudio E. T. Parente; Adan S. Lino; Elias R. Arruda Junior; Everaldo Zonta; Paulo R. Dorneles; João Paulo M. Torres; Rodrigo O. Meire; Olaf Malm (Environmental Monitoring and Assessment, 2019)

Updated checklist and DNA barcode‐based species delimitations reveal taxonomic uncertainties among freshwater fishes from the mid‐north‐eastern Caatinga ecoregion, north‐eastern Brazil - Waldir M. Berbel‐Filho; Telton P. A. Ramos; Uedson P. Jacobina; Danielle J. G. Maia; Rodrigo A. Torres; Sergio M. Q. Lima (Journal of Fish Biology, 2018)
The mid‐north‐eastern Caatinga is a semiarid freshwater ecoregion in North‐eastern Brazil that is dominated by temporary rivers and is currently classified as one of the least ichthyologically‐known ecoregions in the world. The present study aimed to provide an updated checklist of mid‐north‐eastern Caatinga ecoregion (MNCE) freshwater fish species and evaluate their taxonomic identity using morphology, DNA barcoding and multiple species delimitation approaches. After reviewing published studies and ichthyological collections, 119 species were identified. Among these were 94 putatively valid native and 14 non‐native species, five undescribed native species, four new records for the MNCE, 11 potential cases of misidentification and 14 species listed as inquirenda. Additionally, 252 individuals from 49 species were barcoded, revealing three potential taxonomic synonyms. The combined molecular approaches estimated a total of 91 native species, although a finalized species list for the MNCE awaits additional taxonomic revisions and field surveys. This study provides the most up‐to‐date species checklist for the MNCE and a molecular reference database for identifying MNCE fishes with DNA barcodes. Results highlight the need to integrate traditional taxonomy with molecular approaches to correctly identify species, especially in taxonomically problematic ecoregions such as the MNCE.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Clove oil induces anaesthesia and blunts muscle contraction power in three Amazon fish species - Rodrigo Yudi Fujimoto; Débora Martins Pereira; Jessica Cristina Souza Silva; Laís Cássia Araújo de Oliveira; Luis Antonio Kioshi Aoki Inoue; Moisés Hamoy; Vanessa Jóia de Mello; Marcelo Ferreira Torres; Luis André Luz Barbas (Fish Physiology and Biochemistry, 2018)

Development of two artificial neural network models to support the diagnosis of pulmonary tuberculosis in hospitalized patients in Rio de Janeiro, Brazil - Fábio S. Aguiar; Rodrigo C. Torres; João V. F. Pinto; Afrânio L. Kritski; José M. Seixas; Fernanda C. Q. Mello (Medical & Biological Engineering & Computing, 2016)

Carrageenans from nuclear phases of subantartic Mazzaella laminarioides (Gigartinales, Rhodophyta) and graft copolymerization of alkali-modified carrageenan with acrylamide - Franco Arias; Andrés Mansilla; Betty Matsuhiro; Jorge Pavez; Rodrigo Torres; Mauricio Yáñez-Sánchez (Journal of Applied Phycology, 2016)

Ocean acidification induces changes in algal palatability and herbivore feeding behavior and performance - Cristian Duarte; Jorge López; Samanta Benítez; Patricio H. Manríquez; Jorge M. Navarro; Cesar C. Bonta; Rodrigo Torres; Pedro Quijón (Oecologia, 2016)

Inter- and intra-basin phenotypic variation in two riverine cichlids from northeastern Brazil: potential eco-evolutionary damages of São Francisco interbasin water transfer - Waldir M. Berbel-Filho; Pablo A. Martinez; Telton P. A. Ramos; Rodrigo A. Torres; Sergio M. Q. Lima (Hydrobiologia, 2016)

In vitro antifungal activity of silver nanoparticles against fluconazole-resistant Candida species - Jhon J. Artunduaga Bonilla; Daissy J. Paredes Guerrero; Clara I. Sánchez Suárez; Claudia C. Ortiz López; Rodrigo G. Torres Sáez (World Journal of Microbiology and Biotechnology, 2015)

First documented migratory destination for eastern South Pacific blue whales - Juan Pablo Torres‐Florez; Paula A. Olson; Luis Bedriñana‐Romano; Howard Rosenbaum; Jorge Ruiz; Richard LeDuc; Rodrigo Hucke‐Gaete (Marine Mammal Science, 2015)

Fe2+ substrate transport through ferritin protein cage ion channels influences enzyme activity and biomineralization - Rabindra K. Behera; Rodrigo Torres; Takehiko Tosha; Justin M. Bradley; Celia W. Goulding; Elizabeth C. Theil (JBIC Journal of Biological Inorganic Chemistry, 2015)

Cellular Changes Induced by Kinin B1 Receptor Deletion: Study of Endothelial Nitric Oxide Metabolism - Rodrigo A. Loiola; Tathiany C. Torres; Richardt G. Landgraf; João Bosco Pesquero; Liliam Fernandes (International Journal of Peptide Research and Therapeutics, 2015)

Optimization of biomass production of Chlorella vulgaris grown in desalination concentrate - Ângelo Paggi Matos; Weruska Brasileiro Ferreira; Regina Coeli de Oliveira Torres; Luiz Rodrigo Ito Morioka; Maria Helena Machado Canella; Jefferson Rotta; Tiago da Silva; Elisa Helena Siegel Moecke; Ernani Sebastião Sant’Anna (Journal of Applied Phycology, 2015)

CO2-Driven Ocean Acidification Disrupts the Filter Feeding Behavior in Chilean Gastropod and Bivalve Species from Different Geographic Localities - Cristian A. Vargas; Victor M. Aguilera; Valeska San Martín; Patricio H. Manríquez; Jorge M. Navarro; Cristian Duarte; Rodrigo Torres; Marco A. Lardies; Nelson A. Lagos (Estuaries and Coasts, 2015)

Disentangling the controversial identity of the halfbeak stock (Hemiramphus brasiliensis and H. balao) from northeastern Brazil using multilocus DNA markers - Rodrigo A. Torres; Filipe Alberto dos Santos; Flávia R. S. Andrade; Guilherme F. Gondolo; Rosangela P. R. Lessa (Reviews in Fish Biology and Fisheries, 2015)

Intraspecific Variability in the Response of the Edible Mussel Mytilus chilensis (Hupe) to Ocean Acidification - Cristian Duarte; Jorge M. Navarro; Karin Acuña; Rodrigo Torres; Patricio H. Manríquez; Marcos A. Lardies; Cristian A. Vargas; Nelson A. Lagos; Víctor Aguilera (Estuaries and Coasts, 2015)

A Critical Comparison of Different Approaches to Sediment-Quality Assessments in the Santos Estuarine System in Brazil - Ronaldo J. Torres; Augusto Cesar; Victor A. Pastor; Camilo D. S. Pereira; Rodrigo B. Choueri; Fernando S. Cortez; Rodofley D. Morais; Denis M. S. Abessa; Marcos R. L. do Nascimento; Cassia R. Morais; Pedro S. Fadini; Tomas A. Del Valls Casillas; et al. (Archives of Environmental Contamination and Toxicology, 2015)

Reproductive performance of striped mealybug Ferrisia virgata Cockerell (Hemiptera: Pseudococcidae) on water-stressed cotton plants subjected to nitrogen fertilization - Martin D. Oliveira; Paulo R. R. Barbosa; Christian S. A. Silva-Torres; Rodrigo R. Silva; Eduardo M. Barros; Jorge B. Torres (Arthropod-Plant Interactions, 2014)

Primers for the amplification of the MHC IIβ chain exon 2 in the Atlantic goliath grouper (Epinephelus itajara) - Gláucia C. Silva-Oliveira; Anete B. C. Silva; Fabian Blanchard; Zélia Nunes; Rodrigo A. Torres; Iracilda Sampaio; Marcelo Vallinoto (Conservation Genetics Resources, 2014)

Catalase Inhibition Affects Glyoxylate Cycle Enzyme Expression and Cellular Redox Control during the Functional Transition of Sunflower and Safflower Seedlings - Taffarel Melo Torres; Ivanice Bezerra da Silva; Érika Cristina Pinheiro de Castro; Elizeu Antunes dos Santos; Rodrigo Maranguape Silva da Cunha; João Paulo Matos Santos Lima (Journal of Plant Growth Regulation, 2014)

Comparative analysis of five case studies: commonalities and differences in approaches to mitigation actions in five developing countries - Jose Alberto Garibaldi; Harald Winkler; Emilio Lèbre La Rovere; Angela Cadena; Rodrigo Palma; José Eduardo Sanhueza; Emily Tyler; Marta Torres Gunfaus (Climate and Development, 2014)

Bulk atmospheric deposition of persistent toxic substances (PTS) along environmental gradients in Brazil - Rodrigo Ornellas Meire; Admir Créso Targino; João Paulo Machado Torres (Environmental Science and Pollution Research, 2013)

Hidden genetic diversity and distinct evolutionarily significant units in an commercially important Neotropical apex predator, the catfish Pseudoplatystoma corruscans - Daniel C. Carvalho; Denise A. A. Oliveira; Luciano B. Beheregaray; Rodrigo A. Torres (Conservation Genetics, 2012)

Y-SNP haplogroups related to the Yqh+ heteromorphism in the Mexican northwestern population - ENRIQUE JHONATAN ROMO-MARTÍNEZ; GABRIELA MARTÍNEZ-CORTÉS; REYNA LUCÍA BARAJAS-TORRES; RODRIGO RUBI-CASTELLANOS; MARÍA TERESA MAGAÑA-TORRES; HÉCTOR RANGEL-VILLALOBOS; JUAN RAMÓN GONZÁLEZ-GARCÍA (Journal of Genetics, 2012)

Remaining genetic diversity in Brazilian Merganser (Mergus octosetaceus) - Sibelle Torres Vilaça; Rodrigo A. F. Redondo; Livia Vanucci Lins; Fabricio R. Santos (Conservation Genetics, 2012)

Palm Management in South America - Rodrigo Bernal; Claudia Torres; Néstor García; Carolina Isaza; Jaime Navarro; Martha Isabel Vallejo; Gloria Galeano; Henrik Balslev (The Botanical Review, 2011)

Bioethanol production in batch mode by a native strain of Zymomonas mobilis - Laura Pinilla; Rodrigo Torres; Claudia Ortiz (World Journal of Microbiology and Biotechnology, 2011)

Assessment of heavy metals in the particulate matter of two Brazilian metropolitan areas by using Tillandsia usneoides as atmospheric biomonitor - Nelzair A. Vianna; Daniel Gonçalves; Flavia Brandão; Roberta P. de Barros; Gilberto M. Amado Filho; Rodrigo O. Meire; João Paulo M. Torres; Olaf Malm; Argemiro D’Oliveira Júnior; Leonardo R. Andrade (Environmental Science and Pollution Research, 2011)

Environmental Degradation at a Public Park in Southern Brazil as Revealed Through a Genotoxicity Test (MN) on Peripheral Blood Cells from Poecilia vivipara (Teleostei) - Mônica L. Adam; Rodrigo A. Torres; Graziela Sponchiado; Thalita S. Motta; Cíntia M. R. Oliveira; Marco A. Carvalho-Filho; M. T. S. Correia (Water, Air, & Soil Pollution, 2010)

On the Diversity of the Laccase Gene: A Phylogenetic Perspective from Botryosphaeria rhodina (Ascomycota: Fungi) and Other Related Taxa - Flávio J. D. Castilho; Rodrigo A. Torres; Aneli M. Barbosa; Robert F. H. Dekker; José E. Garcia (Biochemical Genetics, 2009)

The remarkable species complex Mimagoniates microlepis (Characiformes: Glandulocaudinae) from the Southern Atlantic Rain forest (Brazil) as revealed by molecular systematic and population genetic analyses - Rodrigo A. Torres; Juliano Ribeiro (Hydrobiologia, 2009)

Evolution of genome size in fishes: a phylogenetic test of the Hinegardner and Rosen hypothesis - Marcio R. Pie; Rodrigo A. Torres; Diego M. A. Brito (Genetica, 2007)